Composite sheet and absorbent article

JP2023153503A5Active Publication Date: 2025-03-14KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022062819
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-05
Publication Date
2025-03-14
Estimated Expiration
2042-04-05

AI Technical Summary

Technical Problem

Conventional composite sheets used in absorbent articles lack optimal combinations of air permeability, moisture permeability, leak-proof properties, elasticity, texture, and appearance, failing to meet the requirements for comfort and functionality.

Method used

A composite sheet is created by laminating a stretchable moisture-permeable film with micropores and a non-stretchable nonwoven fabric, bonded at scattered joints, allowing the nonwoven fabric to expand and contract with the film, creating a convex structure that enhances breathability and elasticity.

Benefits of technology

The composite sheet achieves improved air permeability, moisture permeability, leak-proof properties, and texture, providing enhanced comfort and fit in absorbent articles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a composite sheet excellent in air permeability, moisture permeability, leakage prevention property, elasticity, touch feeling, and appearance.SOLUTION: In a composite sheet 1 of the present invention, an elastic moisture permeable film 2 having a minute hole and a non-elastic non-woven fabric 3 overlap each other and are bonded to each other with a plurality of bonding parts 4 dispersed between overlapping surfaces. The moisture permeable film 2 can extend, and a non-bonding part 31 with the moisture permeable film 2 in the non-woven fabric 3 extends according to extension of the moisture permeable film 2. In a natural state of the moisture permeable film 2, the non-bonding part 31 of the non-woven fabric 3 projects to the side opposite to the moisture permeable film 2 side to form a part or overall of a projection 5.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a stretchable composite sheet in which a stretchable porous moisture-permeable film and a non-stretchable nonwoven fabric are laminated together. [Background technology]

[0002] Moisture-permeable films made of resins having micropores are known. Such moisture-permeable films are generally produced by stretching a resin film containing a filler and an additive to form a large number of micropores. Patent Document 1 describes a moisture-permeable film containing linear low-density polyethylene, branched low-density polyethylene, a filler, and a dispersant for the filler.

[0003] Absorbent articles such as disposable diapers and sanitary napkins typically include a topsheet forming the skin-facing side, a backsheet forming the non-skin-facing side, and an absorbent body disposed between the two sheets, and it is well known that a composite sheet formed by laminating a resin film and a nonwoven fabric is used as a leak-proof sheet forming the non-skin-facing side (outer surface) of an absorbent article, such as the backsheet (Patent Documents 2 to 5).In such composite sheets, the resin film is often placed on the inside (skin-facing side) and the nonwoven fabric is placed on the outside (non-skin-facing side) to ensure that the absorbent article feels good against the skin.

[0004] Patent Document 2 describes the use of a composite sheet consisting of a stretchable sheet made of a thermoplastic synthetic resin elastomer film and a non-stretchable nonwoven fabric as a leak-barrier sheet for a disposable diaper. Patent Document 2 does not describe imparting moisture permeability to the film. Patent Document 3 describes the use of a composite sheet consisting of a non-porous moisture-permeable film and a stretchable nonwoven fabric as a leak-barrier sheet for an absorbent article. Patent Document 4 describes a stretchable composite sheet that can be used as a component of an absorbent article, in which a moisture-permeable film is bonded entirely to one side of a stretchable nonwoven fabric. The composite sheets described in Patent Documents 2 to 4 have, in their natural state without external force, an uneven structure in which ridges and grooves extending in one direction are alternately arranged in a direction perpendicular to the one direction. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 1-144432 [Patent Document 2] Japanese Patent Application Publication No. 10-99373 [Patent Document 3] Japanese Patent Application Laid-Open No. 2004-305771 [Patent Document 4] Japanese Patent Application Laid-Open No. 2008-284717 [Patent Document 5] Japanese Patent Application Publication No. 2019-201691 Summary of the Invention [Problem to be solved by the invention]

[0006] Components such as leak-proof sheets that are positioned relatively far from the wearer's skin in absorbent articles are required to have excellent breathability and moisture permeability to prevent stuffiness while worn, excellent leak-proofness to prevent leakage of body waste, excellent stretchability to improve the fit of the absorbent article, a small number of components, a good feel and appearance, etc. Conventional composite sheets have room for improvement in terms of these required performance characteristics.

[0007] An object of the present invention is to provide a composite sheet that is excellent in breathability, moisture permeability, leak resistance, stretchability, texture, and appearance. [Means for solving the problem]

[0008] The present invention provides a moisture-permeable stretchable film having micropores and a non-stretchable nonwoven fabric, which are overlapped and joined to each other at a plurality of joining portions scattered between the overlapping surfaces, The moisture-permeable film is stretchable, and the portions of the nonwoven fabric that are not joined to the moisture-permeable film stretch in accordance with the stretching of the moisture-permeable film, thereby forming a composite sheet.

[0009] The present invention also relates to an absorbent article comprising the composite sheet of the present invention. [Effects of the Invention]

[0010] According to the present invention, a composite sheet is provided which is excellent in breathability, moisture permeability, leak prevention, stretchability, texture and appearance. [Brief explanation of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic perspective view of one embodiment of the composite sheet of the present invention in its natural state. [Figure 2] FIG. 2 is a cross-sectional view schematically showing a cross section taken along line II in FIG. 1 (a cross section along the thickness direction and the expansion / contraction direction). [Figure 3] FIG. 3 is a schematic perspective view of another embodiment of the composite sheet of the present invention in its natural state. [Figure 4] FIG. 4 is a schematic perspective view of yet another embodiment of the composite sheet of the present invention in its natural state. [Figure 5] FIG. 5 is a photograph corresponding to FIG. 2 of a composite sheet according to still another embodiment of the present invention. [Figure 6] FIG. 6 is a schematic cross-sectional view of a crotch portion of a disposable diaper, which is one embodiment of the absorbent article of the present invention, taken along the lateral and thickness directions. [Figure 7]FIG. 7 is a schematic exploded perspective view of the diaper shown in FIG. DETAILED DESCRIPTION OF THE INVENTION

[0012] The present invention will be described below based on preferred embodiments with reference to the drawings. In the following description of the drawings, the same or similar parts are designated by the same or similar reference numerals. The drawings are basically schematic, and the ratios of the dimensions may differ from those of the actual parts.

[0013] 1 and 2 show a composite sheet 1, which is one embodiment of the composite sheet of the present invention. The composite sheet 1 includes a stretchable moisture-permeable film 2 having micropores and a non-stretchable nonwoven fabric 3. In the composite sheet 1, the moisture-permeable film 2 and the nonwoven fabric 3 overlap and are joined to each other at a plurality of joining sections 4 scattered between the overlapping surfaces. The moisture-permeable film 2 is stretchable, and as the moisture-permeable film 2 stretches, the non-jointed sections 31 of the nonwoven fabric 3 where the moisture-permeable film 2 does not join expands and contracts. In the composite sheet 1, the moisture-permeable film 2 has stretchability in one direction indicated by the symbol Y in the figure, and the composite sheet 1 also has stretchability in the same direction Y.

[0014] The composite sheet 1 is excellent in breathability, moisture permeability, leakproofness, stretchability, feel to the touch, and appearance. The breathability, moisture permeability, leakproofness, and stretchability of the composite sheet 1 are mainly due to the moisture-permeable film 2, and the feel to the touch and appearance are mainly due to the nonwoven fabric 3. Conventional composite sheets of this type include, for example, 1) a combination of a non-porous stretchable moisture-permeable film and a non-stretchable nonwoven fabric, 2) a combination of a porous non-stretchable moisture-permeable film and a non-stretchable nonwoven fabric, and 3) a combination of a moisture-permeable film and a stretchable nonwoven fabric, but 1) has poor breathability because the moisture-permeable film is non-porous, 2) has poor stretchability, and 3) the nonwoven fabric has a poor feel against the skin.In contrast, the composite sheet of the present invention, represented by composite sheet 1, achieves the above-mentioned excellent properties by simply comprising at least one porous stretchable moisture-permeable film and at least one layer of non-stretchable nonwoven fabric. As will be described later, one embodiment of the composite sheet of the present invention employs an olefin resin and an inorganic filler as the main raw materials of the moisture-permeable film, which can achieve the following secondary effects: a) reduced manufacturing costs due to the use of relatively inexpensive raw materials, b) improved bonding strength with synthetic rubber components (e.g., adhesives, pressure-sensitive adhesives, anti-slip agents, etc.) conventionally commonly used in absorbent articles such as disposable diapers and sanitary napkins, c) improved breathability due to the expansion of micropores when the composite sheet is stretched, and d) reduced environmental impact due to reduced resin usage. Advantage d) above means that by having a moisture-permeable film that is porous and contains an inorganic filler, it is possible to reduce the amount of resin used by an amount equivalent to the volume of the inorganic filler and the volume of the pores compared to a moisture-permeable film that is non-porous and made only of resin, thereby mitigating the burden on the environment.

[0015] In the present invention, "stretchable" means the property of being stretchable in a predetermined direction and shrinking when the stretch is released. In the present invention, whether an object has stretchability is evaluated based on the degree of flexible deformation or the residual strain after elongation of the object. Specifically, the following tensile test is carried out on an object (such as a moisture-permeable film or nonwoven fabric) to be evaluated for stretchability, and the measured degree of flexible deformation is 0.060 N / (mm (g / m 2 If the measured flexibility is 0.060 N / (mm·(g / m)) or less, or the measured residual strain after 30% elongation is 11% or less, the object is evaluated as having elasticity in the tensile direction. 2 )) and the measured residual strain after 30% elongation is greater than 11%, the object to be evaluated does not have stretchability in the tensile direction and is evaluated as inelastic. The "stretchable moisture-permeable film" used in this invention is a moisture-permeable film that is stretchable in at least one direction, and the "non-stretchable nonwoven fabric" is a nonwoven fabric that does not have stretchability in the machine direction (the flow direction during the manufacture of the object to be evaluated).

[0016] (Tensile test: measurement of flexibility and residual strain after 30% elongation) A rectangular test piece, 150 mm long in the machine direction (the flow direction during the manufacture of the test piece) and 30 mm long in the width direction perpendicular to the machine direction, was cut out from the test piece to prepare a test piece. The test piece was secured between a pair of gripping jigs in a tensile tester (product name: AG-1S, manufactured by Shimadzu Corporation) so that the machine direction of the test piece was the tensile direction. The test piece was secured so that the length between the pair of gripping jigs, i.e., the machine direction length (initial length) L0 of the test piece before the tensile test, was 100 mm. After securing the test piece, the load read by the tensile tester was set to zero, and the test piece was stretched to 1.3 times L0 at a deformation rate of 200 mm / min (i.e., 30% elongation), and then immediately contracted to L0 at a deformation rate of 200 mm / min. A cyclic test was performed. From the data obtained in the cyclic test, the load (F) at 1.03 times deformation during the elongation process was calculated. 3% ) and calculate the degree of flexible deformation of the test piece [N / (mm (g / m 2 )) is calculated. Flexibility [N / (mm·(g / m 2 ))]=F 3% [N] / (0.03×30[mm]×test piece basis weight [g / m 2 ]) In addition, in the cycle test, the length L1 of the test piece in the machine direction when the load becomes 0.01 [N] or less during the process of shrinking the test piece is measured, and the residual strain of the test piece after 30% elongation is calculated using the following formula. Residual strain after 30% elongation (%)={(L1[mm]-L0[mm]) / L0}× 100 For each type of evaluation object, three test pieces are prepared and the cycle test is carried out on each test piece to calculate the degree of flexible deformation and the residual strain after 30% elongation. The arithmetic mean value of the degrees of flexible deformation of each of the three test pieces is taken as the degree of flexible deformation of the evaluation object, and the arithmetic mean value of the residual strain after 30% elongation of each of the three test pieces is taken as the residual strain after 30% elongation of the evaluation object. If the size of the object to be evaluated is too small to fix the test piece in a rectangular shape in plan view with a machine direction length L of 100 mm and a width direction length of 30 mm, fix the test piece so that it has the largest similarity to such a rectangular shape in plan view. In this case, measure the value of L, set the deformation rate so that the deformation rate per unit sample length is equal, and perform the tensile test. When calculating the degree of flexible deformation, change the width direction length to match the test piece.

[0017] In the composite sheet 1, as shown in FIGS. 1 and 2, in the natural state of the moisture-permeable film 2, Protruding convex portions 5 are formed on the side opposite to the moisture-permeable film 2 side, and part or all of the protruding portions 5 are non-bonded portions 31 of the nonwoven fabric 3. In the present invention, the "natural state" refers to a state in which no external force is applied to the object (moisture-permeable film, composite sheet, etc.). The natural state of the moisture-permeable film 2 is also the natural state of the composite sheet 1.

[0018] In the composite sheet 1, when the moisture-permeable film 2 is in its natural state, a plurality of pleated protrusions 5 (non-bonded portions 31 of the nonwoven fabric 3) extend in a direction intersecting the stretching direction (direction Y) of the moisture-permeable film 2, and between adjacent protrusions 5, 5, recesses 6 having bonded portions 4 at their bottoms extend in the same direction as the protrusions 5. In the illustrated embodiment, the extension direction of the protrusions 5 and recesses 6 is a direction (direction X) perpendicular to the stretching direction of the moisture-permeable film 2. In the natural state of the composite sheet 1, the nonwoven fabric 3 side has an uneven structure with multiple convex portions 5 and concave portions 6 extending in direction X arranged alternately in direction Y, whereas the moisture-permeable film 2 side is flat with essentially no unevenness. The convex portions 5 of the composite sheet 1 are formed by the non-bonded portions 31 of the nonwoven fabric 3 protruding in a direction away from the moisture-permeable film 2, and have hollow portions 7 formed by the gaps between the non-bonded portions 31 and the moisture-permeable film 2. A composite sheet 1 having such hollow structured convex portions 5, i.e., a composite sheet 1 in which the non-jointed portions 31 of the nonwoven fabric 3 are separated from the moisture-permeable film 2 in a natural state to form the convex portions 5, can be produced, for example, by overlapping the nonwoven fabric 3 on the moisture-permeable film 2 in a stretched state and joining them together at the joints 4, and then releasing the moisture-permeable film 2 from its stretched state to return it to its natural state. Thus, in the composite sheet 1, the bonding between the moisture-permeable film 2 and the nonwoven fabric 3 is performed while the moisture-permeable film 2 is in an elongated state, and when the moisture-permeable film 2 is in its natural state, the non-bonded portions 31 of the nonwoven fabric 3 are separated from the moisture-permeable film 2 to form hollow convex portions 5.

[0019] In the composite sheet of the present invention, it is not essential that, in its natural state, the non-joined portions 31 of the nonwoven fabric 3 protrude to the side opposite the moisture-permeable film 2 side to form the convex portions 5. The composite sheet of the present invention also encompasses a form in which, in its natural state, the non-joined portions 31 are not substantially separated from the moisture-permeable film 2 and no convex portions 5 are formed, that is, a form in which both the moisture-permeable film 2 side and the nonwoven fabric 3 side are substantially flat without having an uneven structure.

[0020] Furthermore, in the composite sheet of the present invention, the pattern of the joints 4 (specifically, the positions and planar shape of the joints 4) is not particularly limited, and any pattern can be adopted. The pattern of the joints 4 determines the pattern of the recesses 6 formed at positions corresponding to the joints 4, and in turn determines the pattern of the uneven structure consisting of the protrusions 5 and the recesses 6. 3 and 4 show other embodiments of the uneven structure that can be employed in the composite sheet of the present invention. In the other embodiments described below, configurations that differ from the composite sheet 1 described above will be described, and configurations that are the same as those in the composite sheet 1 will be given the same reference numerals and will not be described again. For configurations that are not specifically described in the other embodiments described below, the description of the composite sheet 1 will be applied as appropriate. 3 differs from the composite sheet 1 in that the protrusions 5 and recesses 6 (joints 4) are arranged irregularly, compared to the composite sheet 1 in which they are arranged regularly. Furthermore, the protrusions 5 of the composite sheet 1 are continuous over the entire length of the composite sheet 1 in the direction X, whereas the protrusions 5 of the composite sheet 1A, although elongated in the direction X, do not extend over the entire length of the composite sheet 1A in the direction X, and recesses 6 exist between the protrusions 5, 5. 4 differs from the composite sheet 1 in that the protrusions 5 have a closed shape in plan view and are surrounded by recesses 6, in that the protrusions 5 extend in one direction from one end of the sheet to the other. The shape of the protrusions 5 in the composite sheet 1B in plan view is not particularly limited, and can be, for example, a circular shape, an elliptical shape, a rectangular shape, or the like. Among the above-described embodiments of the composite sheet, composite sheet 1 in particular has a regular arrangement of convex portions 5 and concave portions 6 as shown in FIG. 1 , which results in a pleasant feel and appearance, and is therefore suitable for applications requiring a pleasant feel and appearance, such as a leak-proof sheet for absorbent articles.

[0021] Fig. 5 shows a photograph of another embodiment of the composite sheet of the present invention, which corresponds to Fig. 2. The protrusions 5 of the composite sheets 1, 1A, and 1B described above had a hollow structure with a hollow portion 7, but the protrusions of the composite sheet shown in Fig. 5 do not have a hollow portion 7 and have a solid structure with the constituent fibers of the nonwoven fabric 3 filled inside. A composite sheet having such solid protrusions 5 can be produced, for example, by overlapping a nonwoven fabric 3 on an unstretched moisture-permeable film 2 and bonding them together at the bonding section 4 to obtain a composite sheet precursor, then introducing the composite sheet precursor into the meshing section of a pair of intermeshing processing members, such as a pair of toothed rollers, and stretching the composite sheet precursor (groove-stretching). The composite sheet precursor introduced into the meshing section is given an "extensibility" by the meshing of one tooth and the bottom of the other processing member, which partially breaks the bonds between the constituent fibers. As a result, the moisture-permeable film 2 and the nonwoven fabric 3 are partially separated, forming non-bonded sections 31, and the composite sheet becomes stretchable in the direction of introduction into the meshing section (the machine direction during composite sheet production). The solid protrusions 5 are the portions given the extensibility by the meshing of the toothed rollers and are more flexible than other portions. Thus, in the composite sheet shown in Figure 5, the moisture-permeable film 2 and the nonwoven fabric 3 are bonded together when the moisture-permeable film 2 is in an unstretched state, and when the moisture-permeable film 2 is in its natural state, the unbonded portions 31 of the nonwoven fabric 3 become part of the solid convex portions 5.

[0022] The composite sheet of the present invention can also be produced by manufacturing methods other than the two manufacturing methods mentioned above, namely, 1) a method comprising the steps of joining a stretchable moisture-permeable film and a non-stretchable nonwoven fabric while the stretched film is in a stretched state, and then releasing the moisture-permeable film from the stretched state (hereinafter also referred to as "manufacturing method A"), and 2) a method comprising the steps of joining a stretchable moisture-permeable film and a non-stretchable nonwoven fabric while the stretched film is in a non-stretched state to obtain a composite sheet precursor, and then subjecting the composite sheet precursor to tooth groove stretching processing (hereinafter also referred to as "manufacturing method B"). For example, the following manufacturing method C can be mentioned. Manufacturing method C includes a shaping step in which a non-stretchable nonwoven fabric is caused to follow the circumferential surface of a rotating uneven roll having an uneven peripheral surface and deformed into an uneven shape; and a step in which the non-stretchable nonwoven fabric deformed into an uneven shape is conveyed while being held on the circumferential surface of the uneven roll, and a step in which a stretched moisture-permeable film is superimposed on the non-stretchable nonwoven fabric during conveyance, and the two are bonded together by adhesive or fusion. In manufacturing method C, as in manufacturing method A, the moisture-permeable film and the nonwoven fabric are bonded while the moisture-permeable film is stretched. Therefore, in the natural state of the composite sheet 1 manufactured by manufacturing method C, the non-bonded portions 31 of the nonwoven fabric 3 are separated from the moisture-permeable film 2, forming hollow convex portions 5. For manufacturing method C, for example, the composite sheet manufacturing method described in JP 2021-79106 A may be appropriately adopted.

[0023] The moisture-permeable film 2 typically contains an olefin resin as a main component and further contains an inorganic filler. The inorganic filler is a substance that forms micropores in the moisture-permeable film 2. Details of the moisture-permeable film 2 will be described later.

[0024] Assuming that the nonwoven fabric 3 is non-stretchable, nonwoven fabrics manufactured by various methods can be used. For example, spunbond nonwoven fabrics, air-through nonwoven fabrics, needle-punched nonwoven fabrics, etc. can be used as the nonwoven fabric 3. The nonwoven fabric 3 may have a single layer structure or a laminate structure in which one or more types of nonwoven fabrics are laminated. Various synthetic fibers, regenerated fibers, and natural fibers can be used as the constituent fibers of the nonwoven fabric 3. Examples of synthetic fibers include fibers made of polyesters such as polyethylene, polypropylene, polyethylene terephthalate, and polybutylene terephthalate, and fibers made of polyamides. Examples of regenerated fibers include fibers made of rayon or cupra. Examples of natural fibers include fibers made of cotton, linen, or silk. The constituent fibers of the nonwoven fabric 3 may be short or long fibers, and may be hydrophilic or water-repellent. Also usable are core-sheath or side-by-side composite fibers, split fibers, modified cross-section fibers, crimped fibers, heat-shrinkable fibers, and the like. These fibers can be used alone or in combination of two or more.

[0025] The nonwoven fabric 3 preferably contains an olefin-based resin. As will be described later, the moisture-permeable film 2 is typically primarily composed of an olefin-based resin. If the nonwoven fabric 3 bonded to the moisture-permeable film 2 contains an olefin-based resin, the bonding strength between them is improved when an adhesive containing synthetic rubber is used, and problems such as peeling during use of the composite sheet 1 can be effectively prevented. For example, a styrene-based thermoplastic elastomer can be used as the synthetic rubber. Therefore, the nonwoven fabric 3 is preferably primarily composed of synthetic fibers made of an olefin-based resin such as ethylene, propylene, or butene.

[0026] There are no particular restrictions on the basis weight of each of the moisture-permeable film 2 and the nonwoven fabric 3, and these may be adjusted appropriately depending on the intended use of the composite sheet 1, etc. For example, when the composite sheet 1 is used as a leak-proof sheet for an absorbent article, the basis weight of the moisture-permeable film 2 is preferably 5 g / m 2 More preferably, 6 g / m 2 or more, and preferably 100 g / m 2 Less than 90 g / m 2 The basis weight of the nonwoven fabric 3 is preferably 5 g / m 2 More preferably, 6 g / m 2 or more, and preferably 100 g / m 2 Less than 90 g / m2 The following is the result.

[0027] The means for forming the joint 4 is not particularly limited, and known joining means such as adhesives and fusion (e.g., heat sealing, ultrasonic sealing, etc.) can be used. Generally, adhesives cause less damage to the moisture-permeable film 2 and nonwoven fabric 3 than fusion, and therefore adhesives are preferred as the joining means. In other words, it is preferred that the moisture-permeable film 2 and nonwoven fabric 3 are joined at the joint 4 with an adhesive. Known adhesives such as hot-melt adhesives can be used as the adhesive.

[0028] When an adhesive is used as a means for joining the moisture-permeable film 2 and the nonwoven fabric 3 at the joint 4, the adhesive preferably contains synthetic rubber. The reason for this is the same as the reason why the nonwoven fabric 3 preferably contains an olefin-based resin, as described above.

[0029] The adhesive to be applied as a means for forming the joint 4 is applied to one or both of the moisture-permeable film 2 and the nonwoven fabric 3. There are no particular restrictions on the adhesive application pattern, but from the perspective of maintaining high breathability and moisture permeability inherent in the moisture-permeable film, it is preferable to apply the adhesive intermittently so that there are areas on the surface to be applied that are not coated with adhesive, rather than applying the adhesive all over the surface to be applied, i.e., solidly. Examples of such intermittent adhesive application patterns include spiral, summit, omega, curtain, and stripe patterns.

[0030] The composite sheet of the present invention is excellent in breathability, moisture permeability, leakproofness, and stretchability, and is therefore useful in applications requiring these properties. Suitable applications of the composite sheet of the present invention include leakproof sheets for absorbent articles such as disposable diapers and sanitary napkins, and waterproof sheets for rainwear. The composite sheet of the present invention is particularly useful as a component of absorbent articles.

[0031] The present invention includes an absorbent article comprising the composite sheet of the present invention. The absorbent article of the present invention broadly includes articles used to absorb body fluids (urine, loose stools, menstrual blood, sweat, etc.) discharged from the human body, such as disposable diapers, sanitary napkins, sanitary shorts, and incontinence pads. The absorbent article of the present invention typically comprises a topsheet forming the skin-facing surface, a backsheet forming the non-skin-facing surface, and a liquid-retaining absorbent core disposed between these two sheets. The absorbent article may further have leakage-proof cuffs on both sides along the longitudinal direction of the skin-facing surface. The absorbent article of the present invention also includes a pants-type absorbent article comprising an absorbent main body including the above-mentioned topsheet, absorbent core, and backsheet, and an outer body disposed on the non-skin-facing side of the absorbent main body. The diaper 10 described below is a pants-type absorbent article. The topsheet is typically liquid-permeable. The absorbent core typically comprises an absorbent core and a core wrap sheet enclosing it. The topsheet, absorbent core, and core wrap sheet may each be any of those commonly used in this type of absorbent article, without any particular restrictions.

[0032] In this specification, the "skin-facing side" refers to the side of the absorbent article or its constituent parts (e.g., backsheet, outer body) that faces the skin of the wearer when the absorbent article is worn, i.e., the side that is relatively closer to the wearer's skin, and the "non-skin-facing side" refers to the side of the absorbent article or its constituent parts that faces the opposite side to the skin when the absorbent article is worn, i.e., the side that is relatively farther from the wearer's skin.

[0033] In the absorbent article of the present invention, the composite sheet of the present invention is preferably used as a leakproof sheet, and is particularly useful as a leakproof sheet that forms the outer surface (non-skin-facing surface) of the absorbent article. Examples of such a leakproof sheet include the backsheet and outer body. One embodiment of the absorbent article of the present invention comprises the composite sheet of the present invention as a leak-barrier sheet that forms the outer surface (non-skin-facing surface) of the absorbent article. In addition, when the composite sheet of the present invention is used as a leakproof sheet in the absorbent article of the present invention, the composite sheet itself may be used as the leakproof sheet, or a laminated sheet of the composite sheet and another sheet material (e.g., nonwoven fabric) may be used as the leakproof sheet.

[0034] 6 and 7 show a pants-type disposable diaper 10, which is one embodiment of the absorbent article of the present invention. The diaper 10 has a longitudinal direction X extending from the wearer's ventral side through the crotch region to the dorsal side, and a transverse direction Y perpendicular to the longitudinal direction X. The diaper 10 is divided into three sections: a crotch region located in the wearer's crotch region, a ventral region located closer to the wearer's ventral side (front side) than the crotch region, and a dorsal region located closer to the wearer's dorsal side (rear side) than the crotch region. The diaper 10 comprises an absorbent main body 11 and an outer body 20 serving as a leak-proof sheet located on the non-skin-facing side of the absorbent main body 11. The diaper 10 is pants-type, with both side edges of the outer body 20 in the longitudinal direction X joined together to form a pair of side seals, a waist opening, and a pair of leg openings.

[0035] The absorbent main body 11 includes a top sheet 12 positioned relatively close to the wearer's skin, a back sheet 13 positioned relatively far from the wearer's skin, and an absorbent body 14 positioned between the two sheets 12, 13. The absorbent body 14 includes an absorbent core 15 and a core wrap sheet 16 that wraps around it. A pair of leak-proof cuffs 17, 17 are provided on both left and right sides of the absorbent main body 11 along the longitudinal direction X, so as to stand up against the wearer's skin when worn.

[0036] As shown in Fig. 7, the outer cover 20 includes a laminate of an outer sheet 21, which forms the non-skin-facing surface (outer surface) of the diaper 1 when worn, and an inner sheet 22 disposed opposite the skin-facing surface of the outer sheet 21. The two sheets 21, 22 are joined together by a joining means such as an adhesive. The inner sheet 22 is composed of a single continuous sheet, while the outer sheet 21 is composed of a combination of multiple sheets. Specifically, the outer sheet 21 includes a ventral outer sheet 21A forming the ventral portion, a dorsal outer sheet 21C forming the dorsal portion, and a crotch outer sheet 21B positioned between the sheets 21A, 21C and forming the crotch portion. The sheets 21A, 21B, and 21C forming the outer sheet 21 are overlapped at their ends in the longitudinal direction X, and are joined together and integrated at the overlapping portions by a known joining means such as an adhesive, heat sealing, high-frequency sealing, or ultrasonic sealing. Elastic members 23 for forming waist gathers are arranged stretchably in the lateral direction Y in the region of the outer body 20 that corresponds to the waist of the wearer, and elastic members 24 for forming leg gathers are arranged stretchably in the region of the outer body 20 that corresponds to the legs of the wearer. The elastic members 23, 24 are sandwiched and fixed between the outer layer sheet 21 and the inner layer sheet 22 by a joining means such as an adhesive.

[0037] The crotch outer layer sheet 21B, which is part of the outer body 20, is formed from the above-mentioned composite sheet 1. In the diaper 10, the crotch outer layer sheet 21B made of the composite sheet 1 is stretchable in the lateral direction Y of the diaper 10, and in the natural state of the composite sheet 1 (moisture-permeable film 2), the nonwoven fabric 3 side has an uneven structure in which a plurality of convex portions 5 and concave portions 6 extending in the longitudinal direction X of the diaper 10 are alternately arranged in the lateral direction Y. The crotch outer layer sheet 21B made of the composite sheet 1 may be stretchable in the longitudinal direction X of the diaper 10. In this case, when the composite sheet 1 (moisture-permeable film 2) is in its natural state, the nonwoven fabric 3 side has an uneven structure in which multiple convex portions 5 and concave portions 6 extending in the transverse direction Y of the diaper 10 are alternately arranged in the longitudinal direction X. Leakproof sheets for the crotch area of ​​absorbent articles, such as the crotch outer layer sheet 21B, are required to have good breathability, moisture permeability, leakproofness, stretchability, feel, and appearance, and therefore the composite sheets of the present invention, represented by composite sheet 1, are useful as leakproof sheets for the crotch area of ​​absorbent articles.

[0038] The composite sheet of the present invention is useful not only as the crotch outer layer sheet 21B, but also as the ventral outer layer sheet 21A and the dorsal outer layer sheet 21C. The ventral outer layer sheet 21A and the dorsal outer layer sheet 21C, particularly the portions of both sheets 21A and 21C that are positioned around the wearer's waist, may require higher breathability than the crotch outer layer sheet 21B. In such cases, one way to improve the breathability of the composite sheet is to form, in addition to the micropores, pores with a larger pore size than the micropores in the moisture-permeable film that constitutes the composite sheet. Forming such pores in the moisture-permeable film raises concerns about a decrease in the leakproofness of the composite sheet. However, since components of absorbent articles that are positioned around the wearer's waist typically do not require leakproofness, if the composite sheet is used in an application that does not require such low leakproofness, it is possible to form, in addition to the micropores, pores in the moisture-permeable film that constitutes the composite sheet. From this viewpoint, the moisture-permeable film constituting the composite sheet of the present invention may have, in addition to the micropores, pores having a larger opening diameter than the micropores, which improves the breathability of the moisture-permeable film and, in turn, the breathability of the composite sheet. From the viewpoint of breathability and strength, the pore size of the moisture-permeable film is preferably 0.5 mm or more, more preferably 0.6 mm or more, and preferably 10 mm or less, more preferably 8 mm or less. On the other hand, the pore size of the micropores in the moisture-permeable film is usually preferably 0.001 μm or more, more preferably 0.005 μm or more, and preferably 500 μm or less, more preferably 300 μm or less. The pore diameter refers to the diameter at the narrowest point of the pore or micropore (the diameter when the pore or micropore has a circular shape in a plan view). The pore diameter can be determined from a microscopic photograph of the pore or micropore. Forming pores in a moisture-permeable film with a larger opening diameter than the micropores can be achieved, for example, by physically drilling holes in the moisture-permeable film by pressing the circumferential surface of a roll having an uneven structure against the moisture-permeable film.

[0039] The composite sheet of the present invention can be used not only as the outer body 20 (outer layer sheet 21) but also as the back sheet 13 in the diaper 10. The composite sheet of the present invention can be used not only in pants-type diapers such as the diaper 10 but also in flat-type diapers, and in such cases, it is preferably used as the back sheet forming the outer surface (non-skin-facing surface) of the flat-type diaper. Flat-type diapers typically have a pair of fastening tapes extending laterally on the back side portion, and when worn, the pair of fastening tapes are fastened to fastening areas provided on the outer surface of the abdominal side portion.

[0040] The moisture-permeable film constituting the composite sheet of the present invention will be described in detail below based on preferred embodiments thereof. Moisture-permeable films have breathability, moisture permeability, leakproofness, and stretchability. Moisture-permeable films are resin films primarily made of resin and have numerous micropores, and the breathability of moisture-permeable films is primarily due to these micropores. The moisture permeability of moisture-permeable films can be exhibited by the resin, but can also be improved by the presence of micropores regardless of whether the resin has moisture permeability or not. The stretchability of moisture-permeable films is primarily due to the resin (for example, the olefin-based resin described below).

[0041] The moisture-permeable film typically contains a resin and an inorganic filler, and is produced by stretching a resin product containing the resin and the inorganic filler to form a large number of micropores in the resin product.

[0042] The resin that is the main raw material of the moisture-permeable film can be a resin that exhibits stretchability when formed into a film, and examples thereof include olefin-based resins, ester-based resins (polyethylene terephthalate, polybutylene terephthalate, etc.), amide-based resins (nylon, etc.), acrylonitrile-based resins, vinyl-based resins, vinylidene-based resins, urethane-based resins, etc., and these can be used alone or in combination of two or more. Of these resins, olefin-based resins are particularly suitable as resins for moisture-permeable films because they can be used to produce high-quality moisture-permeable films at relatively low cost. The olefin resin used in the moisture-permeable film typically contains as its main component a polymer or copolymer of a monoolefin such as ethylene, propylene, or butene. Specific examples include high-density polyethylene, low-density polyethylene, linear low-density polyethylene, and polypropylene.

[0043] From the viewpoint of improving the flexibility of the moisture-permeable film, and therefore the flexibility of the composite sheet of the present invention, the moisture-permeable film preferably contains an olefin-based resin composition having a low density. In this specification, the term "olefin-based resin composition" includes both cases where only one type of olefin-based resin is contained and cases where two or more types of olefin-based resins are contained. The term "olefin-based resin composition" also refers to a concept where the composition is composed only of various olefin-based resins and does not contain other resins or components other than resins. It is not prohibited for the moisture-permeable film used in the present invention to contain resins other than olefin-based resins.

[0044] The olefin resin composition contained in the moisture-permeable film has a density of 0.900 g / cm 3 Preferably, it is less than 0.895 g / cm 3 More preferably, it is 0.885 g / cm or less. 3 It is even more preferred that: The olefin resin composition contained in the moisture-permeable film preferably has a density of 0.840 g / cm 3 If it is above 0.850g / cm, blocking is unlikely to occur in the moisture permeable film. 3 More preferably, it is 0.860 g / cm or more.3 More preferably, it is more than this. In summary, the olefin resin composition contained in the moisture-permeable film has a density of 0.840 g / cm 3 More than 0.900g / cm 3 Preferably, it is less than 0.850 g / cm 3 More than 0.895g / cm 3 More preferably, it is 0.860 g / cm or less. 3 More than 0.885g / cm 3 It is even more preferred that:

[0045] The olefin resin composition contained in the moisture-permeable film preferably contains a low-melting-point olefin resin having a melting point of less than 90° C. (hereinafter simply referred to as "low-melting-point olefin resin") and a high-melting-point olefin resin having a melting point of 95° C. or higher (hereinafter simply referred to as "high-melting-point olefin resin") The low-melting-point olefin resin has the advantage of imparting flexibility to the moisture-permeable film, while the high-melting-point olefin resin has the advantage of being able to solidify the moisture-permeable film obtained by melt molding in a short time, enabling high-speed molding. To further enhance the above-mentioned advantages, the melting point of the low-melting-point olefin resin is preferably 80° C. or lower, more preferably 70° C. or lower. In addition, to obtain dimensional stability of the moisture-permeable film, the melting point of the low-melting-point olefin resin is preferably 40° C. or higher. From the viewpoint of further enhancing the above-mentioned merits, the melting point of the high-melting-point olefin resin is preferably 100°C or higher, more preferably 110°C or higher.

[0046] The melting point of the olefin resin composition contained in the moisture-permeable film is measured by the following method. Using approximately 2.0 mg of moisture-permeable film as a sample, differential scanning calorimetry (DSC) was performed using a differential scanning calorimeter (DSC7000X, Hitachi High-Tech Science Corporation) at a temperature range of 10°C to 260°C, a heating rate of 10°C / min, and in an air environment. The DSC curve obtained shows an endothermic peak that occurs when the olefin-based resin melts, and the melting point of the olefin-based resin is the temperature at the peak of the observed endothermic peak. The melting points of the additives contained in the moisture-permeable film and the olefin-based resin can be distinguished by collecting the additive that bleeds out of the moisture-permeable film and measuring its melting point. The following methods can be used to efficiently collect additives from moisture-permeable films. First, the moisture-permeable film is kneaded for 10 minutes at 160°C and 30 rpm using a Labo Plastomill (manufactured by Toyo Seiki Seisakusho). Next, the resin mass is pressed for 1 minute at 150°C and 13 MPa using a Labo Press (manufactured by Toyo Seiki Seisakusho Seisakusho). It is then cooled and pressed for 1 minute at room temperature and 13 MPa to obtain a pressed film with a thickness of approximately 0.5 mm. Finally, the pressed film is stored in a 50°C environment for 1 week. This allows more additive to bleed out onto the pressed film surface than in the moisture-permeable film, allowing for efficient collection of the additive. Methods for collecting additives from the pressed film surface include, for example, wiping with a wipe or scraping with a spatula.

[0047] The content of the low-melting-point olefin resin in the moisture-permeable film is preferably 30 parts by mass or more, more preferably 35 parts by mass or more, and even more preferably 40 parts by mass or more, per 100 parts by mass of the resin in the moisture-permeable film (specifically, for example, an olefin-based resin composition), from the viewpoint of imparting satisfactory flexibility to the moisture-permeable film while maintaining small residual strain after elongation deformation. Furthermore, the content is preferably 95 parts by mass or less, more preferably 92 parts by mass or less, and even more preferably 90 parts by mass or less, from the viewpoint of making the moisture-permeable film less susceptible to blocking. The content of the high-melting-point olefin resin in the moisture-permeable film is preferably 5 parts by mass or more, more preferably 8 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the resin in the moisture-permeable film (specifically, for example, an olefin-based resin composition), from the viewpoint of imparting better heat resistance, morphological stability, and processability to the moisture-permeable film. Furthermore, the content is preferably 70 parts by mass or less, more preferably 65 parts by mass or less, and even more preferably 60 parts by mass or less, from the viewpoint of achieving compatibility with the flexibility of the moisture-permeable film.

[0048] The density of the low-melting-point olefin resin is preferably 0.895 g / cm from the viewpoint of improving the flexibility of the moisture-permeable film. 3 or less, more preferably 0.885 g / cm 3 or less, more preferably 0.875 g / cm 3 The following is the result. Furthermore, the density of the low-melting-point olefin resin is preferably 0.840 g / cm from the viewpoint of maintaining the strength of the moisture-permeable film. 3 More preferably, 0.850 g / cm 3 More preferably, 0.860 g / cm 3 That's all. In summary, the density of the low-melting-point olefin resin is preferably 0.840 g / cm 3 , assuming that the density is lower than the density of the high-melting-point olefin resin used in combination. 3 More than 0.895g / cm 3 or less, more preferably 0.850 g / cm 3 More than 0.885g / cm 3 More preferably, 0.860 g / cm 3 More than 0.875g / cm 3 The following is the result. A preferred example of the low-melting-point olefin-based resin is a copolymer of ethylene and an α-olefin, and examples of the α-olefin include propylene, 1-butene, 1-pentene, and 1-hexene. From the viewpoint of reliably adjusting the melting point and density of the low-melting-point olefin-based resin within the above-mentioned preferred ranges, the low-melting-point olefin-based resin is preferably a random copolymer. In particular, a copolymer of ethylene and an α-olefin polymerized using a metallocene catalyst is more preferred because it further improves the strength of the film against tearing, puncture, etc.

[0049] The density of the high-melting-point olefin resin is preferably relatively low, and more preferably 0.950 g / cm 3 , from the viewpoint of achieving both flexibility and moisture permeable film. 3 or less, more preferably 0.940 g / cm 3 or less, more preferably 0.930 g / cm 3 The following is the result. The density of the high-melting-point olefin resin is preferably 0.900 g / cm from the viewpoint of suppressing blocking. 3 More preferably, 0.905 g / cm 3 More preferably, 0.910 g / cm 3 That's all. In summary, the density of the high-melting-point olefin resin is preferably 0.900 g / cm 3 , assuming that the density is higher than the density of the low-melting-point olefin resin used in combination. 3 More than 0.950g / cm 3 or less, more preferably 0.905 g / cm 3 More than 0.940g / cm 3 , and more preferably 0.910 g / cm 3 More than 0.930g / cm 3 The following is the result. As the high-melting-point olefin resin, low-density polyethylene and linear low-density polyethylene are preferably used, and linear low-density polyethylene is particularly preferred from the viewpoints of improving heat resistance during stretching and enabling uniform stretching. In particular, linear low-density polyethylene polymerized with a metallocene catalyst is more preferred because it further improves the strength of the film against tearing, puncture, etc.

[0050] In the moisture-permeable film, the inorganic filler is a substance that causes peeling at the interface with the resin used in combination, forming micropores. From the viewpoint of ensuring that the inorganic filler functions as described above, the average particle size D50 of the inorganic filler is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 30 μm or less, more preferably 10 μm or less. The average particle size D50 of the inorganic filler is the weight cumulative particle size at a cumulative weight of 50% by mass as determined by a laser diffraction / scattering particle size distribution measurement method.

[0051] Examples of inorganic fillers include calcium carbonate, gypsum, talc, clay, kaolin, silica, diatomaceous earth, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, calcium phosphate, aluminum hydroxide, zinc oxide, titanium oxide, alumina, mica, zeolite, carbon black, and mixtures thereof. Calcium carbonate is particularly preferred because its average particle size D50 can be easily adjusted to fall within the above-mentioned preferred range.

[0052] From the viewpoint of the balance between the breathability, moisture permeability, and leak prevention properties of the moisture-permeable film, the content of the inorganic filler in the moisture-permeable film is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, even more preferably 80 parts by mass or more, and preferably 400 parts by mass or less, more preferably 350 parts by mass or less, and even more preferably 200 parts by mass or less, relative to 100 parts by mass of the resin in the moisture-permeable film. If the content of the inorganic filler is too low, the size and number of the micropores may be insufficient, resulting in insufficient breathability and moisture permeability, while if the content of the inorganic filler is too high, there is a risk of a decrease in leak prevention properties.

[0053] The moisture-permeable film may further contain a pore-opening promoter in addition to the above-mentioned resin (preferably an olefin-based resin composition) and inorganic filler. The pore-opening promoter is used for the purpose of smoothly forming micropores by stretching a resin sheet containing a resin and an inorganic filler. As mentioned above, from the viewpoint of improving the flexibility of the moisture-permeable film, it is preferable for the moisture-permeable film to contain a low-melting-point olefin-based resin. However, since low-melting-point olefin-based resins are resins that are relatively unlikely to undergo interfacial peeling with inorganic fillers, using a pore-opening promoter in addition to the low-melting-point olefin-based resin as a raw material for the moisture-permeable film can promote such interfacial peeling. As the pore opening promoter, a substance known as a mold release agent between metal and resin is preferably used. Specific examples include metal soap, silicone, fluororesin, fatty acid amide, hydrocarbon paraffin wax, etc. In particular, it is preferable to use metal soap because it can more smoothly form micropores. The metal soap is preferably a metal salt of a fatty acid. Examples of the fatty acid include caprylic acid, palmitic acid, stearic acid, capric acid, oleic acid, myristic acid, and lauric acid. Examples of the metal salt include salts of calcium, aluminum, magnesium, zinc, etc., of these fatty acids. In particular, it is preferable that the chain length of the hydrocarbon chain in the fatty acid added to hydrophobize the surface of the inorganic filler (described later) is the same as the chain length of the hydrocarbon chain in the fatty acid constituting the metallic soap, since this allows the metallic soap to migrate more smoothly to the inorganic filler whose surface has been modified with the fatty acid. In particular, it is preferable that both the fatty acid and the fatty acid constituting the metallic soap are stearic acid. Fatty acids themselves are known as substances similar to metal salts of fatty acids and are incorporated into moisture-permeable films. Fatty acids are used to enhance the dispersibility of inorganic fillers. However, fatty acids do not promote interfacial delamination between resins and inorganic fillers. Therefore, in the present invention, metal salts of fatty acids and fatty acids are clearly distinguished from each other both physically and functionally.

[0054] In particular, it is preferable to use a metal soap with a melting point of 200°C or less, because the metal soap melts sufficiently and is uniformly mixed into the molten resin when kneading the resin-containing compound in the moisture-permeable film manufacturing process. From this viewpoint, the melting point of the metal soap is more preferably 180°C or less, and even more preferably 160°C or less.

[0055] Furthermore, in relation to the resin described above, it is preferable to use a metal soap whose precipitation temperature is higher than the solidification temperature of the resin, from the viewpoint of successfully forming micropores and obtaining a moisture-permeable film with high moisture permeability and high water resistance. Specifically, when the precipitation temperature of the metal soap is higher than the solidification temperature of the resin, the metal soap precipitates faster than the resin solidifies, allowing the metal soap to smoothly migrate to the surface of the inorganic filler. As a result, the releasability between the inorganic filler and the resin during stretching is improved, and micropores are smoothly formed. To further enhance this advantage, when the precipitation temperature of the metal soap is Ts (°C) and the solidification temperature of the resin is Tp (°C), the value of Ts - Tp is preferably greater than 0°C, more preferably 1°C or greater, and even more preferably 2°C or greater. Furthermore, the value of Ts - Tp is preferably 50°C or less.

[0056] Provided that the value of Ts-Tp is within the aforementioned range, the deposition temperature Ts of the metal soap is preferably 80°C or higher and 180°C or lower, more preferably 90°C or higher and 170°C or lower, and even more preferably 100°C or higher and 160°C or lower. On the other hand, the solidification temperature Tp of the resin is preferably 60°C or higher and 130°C or lower, more preferably 70°C or higher and 120°C or lower, and even more preferably 80°C or higher and 115°C or lower, provided that the value of Ts-Tp is within the above-mentioned range.

[0057] The metal soap precipitation temperature Ts is measured using a hot stirrer and a thermocouple as follows: Using a hot stirrer, 0.43 g of metal soap is added to 5.0 g of paraffin oil, and the mixture is heated while stirring until the metal soap dissolves. After stirring the liquid with the stirrer is stopped, the temperature of the paraffin oil is lowered at a rate of 0.2°C / min, and the temperature of the paraffin oil when the metal soap begins to precipitate is read with a thermocouple, and this temperature is defined as the metal soap precipitation temperature. Note that if the metal soap does not dissolve in the paraffin oil even after heating the paraffin oil to 210°C, the precipitation temperature is defined as 210°C. The resin solidification temperature, Tp, is measured according to JIS K 7121 (Method for determining the extrapolated crystallization end temperature) using the following method. Approximately 2.0 mg of moisture-permeable film is used as a sample. Differential scanning calorimetry (DSC) is performed using a differential scanning calorimeter (DSC7000X, Hitachi High-Tech Science Corporation) under the following conditions: a temperature range of 30°C to 260°C, a heating rate of 10°C / min, a cooling rate of 50°C / min, an air environment, and a data sampling period of 0.5 s. During the cooling process of the obtained DSC curve, an exothermic peak is observed, which occurs when the resin solidifies (crystallizes). The resin solidification temperature is determined as the temperature at the intersection of a line drawn by extending the baseline on the lower side of the peak temperature toward the higher side, relative to the peak with the highest heat release during the cooling process, and an approximation line drawn between the two data points with the greatest slope on the lower side of the peak. When two or more overlapping exothermic peaks exist, the peaks are separated using, for example, software PeakFit v4.12 (manufactured by Hulinks Co., Ltd.), and then the solidification temperature is determined by the above-mentioned method.

[0058] The content of the pore opening promoter in the moisture-permeable film is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, per 100 parts by mass of the resin in the moisture-permeable film, from the viewpoint of promoting the formation of micropores, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, from the viewpoint of obtaining good film formability.

[0059] Furthermore, when the moisture-permeable film contains an inorganic filler and the pore opening promoter in the moisture-permeable film is a metal soap, the content of the metal soap in the moisture-permeable film is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more, per 100 parts by mass of the inorganic filler in the moisture-permeable film, from the viewpoint of being able to successfully generate micropores. And, from the viewpoint of maintaining good moldability, it is preferably 10 parts by mass or less, more preferably 9 parts by mass or less, and even more preferably 8 parts by mass or less.

[0060] The moisture-permeable film may further contain a triglyceride in addition to the resin (preferably an olefin-based resin composition), inorganic filler, and, if necessary, a pore-opening promoter. The triglyceride can function as a water-repellent agent that improves the water repellency and leak-proofness of the moisture-permeable film. In the technical field of moisture-permeable films used in the present invention, triglycerides have been blended into moisture-permeable films up to now, but the triglyceride used in the present invention is preferably of a different type from the triglycerides that have been used up to now in that technical field. In particular, the triglyceride preferably used in the present invention is "a triglyceride that contains a group derived from a fatty acid having from 16 to 22 carbon atoms, and the group is a hydrocarbon group that has no unsaturated bond or substituent" (hereinafter also referred to as "specific triglyceride"). As a result of investigations by the present inventors, it was found that the use of the specific triglyceride improves the water repellency of moisture-permeable films containing the specific triglyceride, and improves the leakproofness of the moisture-permeable films more than ever before.

[0061] In order to make the above-mentioned advantages more pronounced, the content of the specific triglyceride in the moisture-permeable film is preferably 0.1 parts by mass or more per 100 parts by mass of the resin, more preferably 0.5 parts by mass or more, and even more preferably 1.0 part by mass or more. Furthermore, from the viewpoint of film formability, the content of the specific triglyceride is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the resin. Taking all of the above into consideration, the content of the specific triglyceride is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 25 parts by mass or less, and even more preferably 1.0 parts by mass or more and 20 parts by mass or less, per 100 parts by mass of the resin.

[0062] Furthermore, from the viewpoint of fully exerting the effects of both the metal soap used as a pore-opening promoter and the water repellent, and from the viewpoint of preventing deterioration of processability due to excessive inclusion of additives, the ratio of the specific triglyceride to the metal soap contained in the moisture-permeable film is preferably 30 to 300 parts by mass of the metal soap per 100 parts by mass of the specific triglyceride. To make this advantage even more pronounced, the metal soap is used in an amount of preferably 35 to 230 parts by mass, and even more preferably 40 to 220 parts by mass, per 100 parts by mass of the specific triglyceride.

[0063] The specific triglyceride will be explained below. The specific triglyceride is represented by the following formula (1).

[0064] [ka]

[0065] In the formula (1), R 1 , R 2 , R 3 R represents the same or different hydrocarbon groups. 1 , R 2 , R 3 At least one of the groups is a group derived from a fatty acid having 16 to 22 carbon atoms, and the group is a hydrocarbon group having no unsaturated bond or substituent. The alkyl group of palmitic acid, a fatty acid having 16 carbon atoms, has 15 carbon atoms. The "hydrocarbon group having no unsaturated bonds" refers to a hydrocarbon group having neither a carbon-carbon double bond nor a triple bond. In other words, it refers to an alkyl group. Furthermore, the "hydrocarbon group having no substituents" refers to a hydrocarbon group in which the hydrogen atoms contained in the hydrocarbon group are not substituted with other atoms or atomic groups (e.g., hydroxyl groups). Therefore, the "hydrocarbon group having no unsaturated bonds or substituents" is synonymous with an unsubstituted alkyl group.

[0066] In the specific triglyceride represented by the formula (1), from the viewpoint of obtaining a moisture-permeable film having higher water repellency, R 1 , R 2 , R 3 At least one of the groups is a group derived from a fatty acid having 16 to 20 carbon atoms, and the group is preferably a hydrocarbon group having no unsaturated bond and no substituent. In addition, in the specific triglyceride represented by the formula (1), R 1 , R 2 , R 3 When any one or two of the above is a group other than a group derived from a fatty acid having from 16 to 22 carbon atoms (the group is a hydrocarbon group having no unsaturated bond and no substituent), there are no particular restrictions on the type of the group as long as it is a group derived from a fatty acid, but from the viewpoint of obtaining a moisture-permeable film with even higher water repellency, it is preferable that the group has no unsaturated bond and no substituent.

[0067] The specific triglyceride is preferably one in which the number of carbon atoms in the fatty acid residue is adjusted. This can enhance the water repellency of the moisture-permeable film. Specifically, the specific triglyceride is preferably (A) or (B) below. (A) A triglyceride containing a mixture of a triglyceride containing at least a group derived from a fatty acid having 18 carbon atoms in one molecule and a triglyceride containing at least a group derived from a fatty acid having 16 to 22 carbon atoms in one molecule (excluding fatty acids having 18 carbon atoms). (B) A triglyceride containing, in one molecule, at least one group derived from a saturated fatty acid having 18 carbon atoms and at least one group derived from a saturated fatty acid having 16 to 22 carbon atoms (excluding fatty acids having 18 carbon atoms). In particular, from the viewpoint of further enhancing liquid repellency, it is preferable that the triglyceride contains, in one molecule, at least one group derived from a saturated fatty acid having 18 carbon atoms and at least one group derived from a saturated fatty acid having 16 to 22 carbon atoms (excluding fatty acids having 18 carbon atoms). As a specific example, a combination of a fatty acid having 18 carbon atoms and a fatty acid having 16 carbon atoms is as shown in (C) or (D) below. (C) A triglyceride containing a mixture of a triglyceride containing at least a group (the group is a hydrocarbon group having no unsaturated bonds and no substituents) derived from a fatty acid having 18 carbon atoms (i.e., stearic acid) in one molecule, and a triglyceride containing at least a group (the group is a hydrocarbon group having no unsaturated bonds and no substituents) derived from a fatty acid having 16 carbon atoms (i.e., palmitic acid) in one molecule. (D) A triglyceride containing, in one molecule, at least one group derived from a fatty acid having 18 carbon atoms (the group is a hydrocarbon group having no unsaturated bonds or substituents) and at least one group derived from a fatty acid having 16 carbon atoms (the group is a hydrocarbon group having no unsaturated bonds or substituents).

[0068] As in the case of (C) above, when the specific triglyceride includes multiple types of triglycerides, it is preferable that at least one of the triglycerides contains at least one group derived from a saturated fatty acid having 16 carbon atoms in one molecule (this triglyceride is also referred to as "triglyceride 16"). Triglyceride 16 may contain one group derived from a saturated fatty acid having 16 carbon atoms in one molecule (this triglyceride is also referred to as "triglyceride P"), two groups (this triglyceride is also referred to as "triglyceride PP"), or three groups (this triglyceride is also referred to as "triglyceride PPP"). The type of the remaining fatty acid residue in triglyceride P and triglyceride PP is not particularly limited, and may be, for example, a residue of a saturated fatty acid having 12 to 24 carbon atoms.

[0069] Triglyceride 16 may consist solely of triglyceride P, may consist solely of triglyceride PP, or may consist solely of triglyceride PPP. Triglyceride 16 may be a combination of two or more selected from triglyceride P, triglyceride PP, and triglyceride PPP. For example, triglyceride 16 may be a combination of triglyceride P and triglyceride PP, a combination of triglyceride P and triglyceride PPP, a combination of triglyceride PP and triglyceride PPP, or a combination of triglyceride P, triglyceride PP, and triglyceride PPP.

[0070] As in the case of (C) above, when the specific triglyceride includes multiple types of triglycerides, it is also preferred that at least one of the triglycerides contains at least one group derived from a saturated fatty acid having 18 carbon atoms in one molecule (this triglyceride is also referred to as "triglyceride 18"). Triglyceride 18 may contain one group derived from a fatty acid having 18 carbon atoms in one molecule (this triglyceride is also referred to as "triglyceride S"), two groups (this triglyceride is also referred to as "triglyceride SS"), or three groups (this triglyceride is also referred to as "triglyceride SSS"). The type of the remaining fatty acid residue in triglyceride S and triglyceride SS is not particularly limited, and may be, for example, a residue of a saturated fatty acid having 12 to 24 carbon atoms.

[0071] Triglyceride 18 may consist solely of S triglycerides, may consist solely of SS triglycerides, or may consist solely of SSS triglycerides. Triglyceride 18 may be a combination of two or more selected from triglyceride S, triglyceride SS, and triglyceride SSS. For example, triglyceride 18 may be a combination of triglyceride S and triglyceride SS, a combination of triglyceride S and triglyceride SSS, a combination of triglyceride SS and triglyceride SSS, or a combination of triglyceride S, triglyceride SS, and triglyceride SSS.

[0072] In the case of (C) above, the specific triglyceride may consist solely of triglyceride 16 and triglyceride 18, or may comprise other triglycerides in addition to triglyceride 16 and triglyceride 18. Examples of other triglycerides include triglycerides that have no groups derived from fatty acids having from 14 to 22 carbon atoms, and triglycerides that contain groups derived from fatty acids having from 14 to 22 carbon atoms (excluding triglyceride 16 and triglyceride 18).

[0073] If a group derived from a saturated fatty acid having 16 carbon atoms is designated "P," a group derived from a saturated fatty acid having 18 carbon atoms is designated "S," and groups derived from a fatty acid other than a saturated fatty acid having 16 carbon atoms and a saturated fatty acid having 18 carbon atoms are designated "X" and "Y," examples of combinations of aliphatic groups that constitute specific triglycerides include PPP, SSS, PPX, SSX, PXY, SXY, PPS, PSS, and PSX. The structures of triglycerides represented by PPX, SSX, PXY, SXY, and PSX are (a) to (m) below. Note that the structures of PPS and PSS are not shown, but the structure of PPS conforms to the structure of PPX, and the structure of PSS conforms to the structure of SSX.

[0074] [ka]

[0075] [ka]

[0076] [ka]

[0077] [ka]

[0078] [ka]

[0079] The specific triglyceride may be any of the various triglycerides described above. For example, in the case of (D), the specific triglyceride may be composed of a triglyceride containing, in one molecule, at least one group derived from a saturated fatty acid having 16 carbon atoms and at least one group derived from a saturated fatty acid having 18 carbon atoms, but containing no groups derived from other fatty acids. Alternatively, the specific triglyceride may be composed of a triglyceride containing one group derived from a saturated fatty acid having 16 carbon atoms, one group derived from a saturated fatty acid having 18 carbon atoms, and one group derived from another fatty acid.

[0080] The specific triglyceride may be a combination of two or more of the various triglycerides described above. For example, the specific triglyceride may be a combination of (C) and (D) above. Alternatively, the specific triglyceride may be a combination of two or more of (D) above. Furthermore, the specific triglyceride may be a combination of one or more of the above-mentioned triglycerides with other triglycerides, such as triglycerides containing a group derived from a fatty acid having 14 to 22 carbon atoms (excluding triglyceride 16 and triglyceride 18). In the present invention, it is preferred to use the above-mentioned various triglycerides alone or to use a combination of two or more of the above-mentioned various triglycerides alone, from the viewpoint of further increasing the water repellency of the moisture-permeable film.

[0081] From the viewpoint of obtaining a moisture-permeable film with even higher water repellency, it is preferred that the triglycerides contained in the moisture-permeable film used in the present invention have 28% by mass or more and 96% by mass or less, particularly 28% by mass or more and 70% by mass or less, and especially 29% by mass or more and 67% by mass or less, of the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film, be groups derived from fatty acids having 18 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds or substituents). The above-mentioned "all triglycerides" is a general term for the specific triglycerides contained in the moisture-permeable film and triglycerides other than the specific triglycerides (hereinafter the same unless otherwise specified).

[0082] Furthermore, from the viewpoint of further increasing the water repellency of the moisture-permeable film and shortening the time until water repellency is achieved, it is preferable that the triglycerides contained in the moisture-permeable film used in the present invention have, relative to the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film, 28% by mass to 68% by mass of groups derived from fatty acids having 18 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds or substituents) and 26% by mass to 70% by mass of groups derived from fatty acids having 16 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds or substituents), provided that the sum of the proportion of groups derived from fatty acids having 18 carbon atoms and the proportion of groups derived from fatty acids having 16 carbon atoms does not exceed 100% by mass. In this case, the proportion of groups derived from fatty acids having 18 carbon atoms is more preferably 29% by mass or more and 66% by mass or less, and even more preferably 30% by mass or more and 64% by mass or less. On the other hand, the proportion of groups derived from fatty acids having 16 carbon atoms is more preferably 27% by mass or more and 69% by mass or less, and even more preferably 28% by mass or more and 68% by mass or less. The higher the proportion of groups derived from fatty acids having 16 carbon atoms, the more easily triglycerides are precipitated on the surface of the moisture-permeable film, and the shorter the time until water repellency is achieved.

[0083] Furthermore, from the viewpoint of improving the thermal stability of the moisture-permeable film and further increasing the water repellency of the moisture-permeable film, it is preferable that the triglycerides contained in the moisture-permeable film of the present invention have, relative to the total amount of groups derived from fatty acids contained in all triglycerides, 28% by mass to 47% by mass of groups derived from fatty acids having 18 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds or substituents) and 40% by mass to 60% by mass of groups derived from fatty acids having 22 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds or substituents), provided that the sum of the proportion of groups derived from fatty acids having 18 carbon atoms and the proportion of groups derived from fatty acids having 22 carbon atoms does not exceed 100% by mass. In this case, the proportion of groups derived from fatty acids having 18 carbon atoms is more preferably 30% by mass or more and 45% by mass or less, and even more preferably 32% by mass or more and 43% by mass or less. On the other hand, the proportion of groups derived from fatty acids having 22 carbon atoms is more preferably 42% by mass or more and 58% by mass or less, and even more preferably 44% by mass or more and 56% by mass or less. The higher the proportion of groups derived from fatty acids having 22 carbon atoms, the higher the melting point of the triglyceride and the higher the thermal stability of the molded product. Furthermore, contamination of the rolls of the processing machine can be reduced.

[0084] The proportions of groups derived from fatty acids having 16 carbon atoms, groups derived from fatty acids having 18 carbon atoms, and groups derived from fatty acids having 22 carbon atoms, based on the total amount of groups derived from fatty acids contained in all triglycerides, are measured by the following method. The triglycerides that bleed out onto the surface of the film are collected by wiping with a cellulose wiper. The ester bonds in the obtained triglycerides are hydrolyzed with alkali, and the methyl-esterified fatty acids are quantitatively analyzed by gas chromatography.

[0085] The presence of alkyl chains with different carbon numbers within a single triglyceride molecule can be determined using TOF-MS (time-of-flight mass spectrometry). Specifically, the molecular weight distribution of triglycerides is measured using TOF-MS, and the presence of alkyl groups with different carbon numbers within the molecule can be determined from the molecular weight of the single molecule. The presence of alkyl chains with different carbon numbers within a single molecule of a compound with the same molecular weight can be determined using a tandem mass spectrometer (MS / MS). Specific ions are selected in the first mass separation section, and the fragment ions generated by colliding with an inert gas are separated and detected in the second mass separation section to determine the presence of alkyl chains with different carbon numbers within the molecule.

[0086] The triglyceride used in the present invention preferably does not contain groups derived from unsaturated fatty acids, from the viewpoint of further increasing the water repellency of the moisture-permeable film. "Doing not contain groups derived from unsaturated fatty acids" encompasses both cases where no groups derived from unsaturated fatty acids are contained at all, and cases where a small amount of unsaturated fatty acids is inevitably contained. "Inevitably containing a small amount of unsaturated fatty acids" refers to, for example, cases where the proportion of groups derived from unsaturated fatty acids is 2% by mass or less, based on the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film.

[0087] As mentioned above, it is preferable that the triglyceride used in the present invention does not contain any groups derived from fatty acids having hydroxyl groups, from the viewpoint of further increasing the water repellency of the moisture-permeable film. A fatty acid having a hydroxyl group is a fatty acid in which at least one hydrogen atom in the hydrocarbon group of the fatty acid is substituted with a hydroxyl group. "Not containing any groups derived from fatty acids having hydroxyl groups" encompasses both cases in which no groups derived from fatty acids having hydroxyl groups are contained at all, and cases in which small amounts of groups derived from fatty acids having hydroxyl groups are unavoidably contained. An example of a case in which small amounts of groups derived from fatty acids having hydroxyl groups are those in which the proportion of groups derived from fatty acids having hydroxyl groups is 2% by mass or less, based on the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film.

[0088] From the viewpoint of further increasing the water repellency of the moisture-permeable film used in the present invention, it is preferable that in the moisture-permeable film, the groups derived from fatty acids contained in all triglycerides are hydrocarbon groups having no unsaturated bonds, and it is also preferable that the groups derived from fatty acids contained in all triglycerides are hydrocarbon groups having no substituents.

[0089] The moisture-permeable film used in the present invention may contain only triglycerides as glycerides, or may contain monoglycerides and / or diglycerides in addition to triglycerides as long as the desired effects of the present invention are achieved.

[0090] The moisture-permeable film may contain components other than the aforementioned resins such as olefin-based resins, inorganic fillers, pore-opening promoters, and specific triglycerides. Examples of such components include dispersants for inorganic fillers, plasticizers, antioxidants, ultraviolet absorbers, colorants, etc. Dispersants and plasticizers are particularly useful in imparting various additional properties to the moisture-permeable film.

[0091] Dispersants that can hydrophobize the surface of inorganic fillers are preferably used. From this viewpoint, it is preferable to use fatty acids as dispersants. Examples of fatty acids include caprylic acid, palmitic acid, stearic acid, capric acid, oleic acid, myristic acid, and lauric acid.

[0092] The plasticizer is used to impart flexibility and suppleness to the moisture-permeable film and to prevent rustling noise from occurring in the moisture-permeable film. Preferred plasticizers include monoesters, polyesters, ethylene-α-olefin co-oligomers, low-molecular-weight polyethylenes, olefin oligomers, liquid polyisoprene, and liquid polybutadiene. Monoesters are compounds obtained from monobasic acids and monohydric alcohols. On the other hand, polyester is a compound obtained by combining any one of polybasic acid and monohydric alcohol, monobasic acid and polyhydric alcohol, and polybasic acid and polyhydric alcohol. Ethylene-alpha olefin co-oligomers are low molecular weight copolymers of ethylene with alpha olefins such as propylene, 1-butene, 1-pentene, and 1-hexene. As the basic acid, polybasic acid, monohydric alcohol, and polyhydric alcohol, for example, the following are preferably used. Examples of monobasic acids include monocarboxylic acids of long-chain hydrocarbons having 10 to 22 carbon atoms. Examples of polybasic acids include dicarboxylic acids, tricarboxylic acids, and tetracarboxylic acids. Examples of monohydric alcohols include monoalcohols of long-chain hydrocarbons having 10 to 22 carbon atoms. Examples of polyhydric alcohols include diols, trimethylolpropane, pentaerythritol, dipentaerythritol, sorbitol, and sucrose.

[0093] Particularly preferred examples of polyesters as plasticizers include polyesters of diethylene glycol and dimer acid in which the carboxylic acid or alcohol at both ends is partially or completely blocked with stearyl alcohol or stearic acid, polyesters of 1,3-butanediol and adipic acid, hexaesters of trimethylolpropane-adipic acid-stearic acid, octaesters of pentaerythritol-adipic acid-stearic acid, and dodecaesters of dipentaerythritol-adipic acid-stearic acid.

[0094] Furthermore, particularly preferred examples of monoesters as plasticizers include esters having a total of 30 or more carbon atoms obtained by dehydration of a monocarboxylic acid having 1 to 40 carbon atoms and a monoalcohol having 1 to 40 carbon atoms. Among these, those having a total of 30 or more carbon atoms obtained from a monocarboxylic acid and a monoalcohol are preferred, and monoesters having 38 or more carbon atoms and having a branched chain are more preferred. Specific examples include isodecyl stearate, isodecyl behenate, isotridecyl stearate, 2-octadecyl stearate, 2-decyltetradecyl laurate, 2-decyltetradecyl stearate, 2-octadecyl behenate, stearyl isostearate, esters of stearic acid and C20 Guerbet alcohol, and esters of α-branched fatty acids (having 18 to 40 carbon atoms) and monoalcohols (having 6 to 36 carbon atoms).

[0095] The content of dispersant and plasticizer in the moisture-permeable film is preferably 0.01 parts by mass or more, more preferably 0.10 parts by mass or more, even more preferably 2.0 parts by mass or more, and preferably 18.0 parts by mass or less, more preferably 16.0 parts by mass or less, per 100 parts by mass of resin in the moisture-permeable film, from the viewpoint of clarifying the purpose of their use while suppressing the adverse effects that may occur when they are used in excess (for example, a decrease in the formability or strength of the film).

[0096] Additives other than the specific triglyceride (such as pore-opening promoters, dispersants, and plasticizers) that can be contained in the moisture-permeable film may include at least a first additive whose SP value differs from that of the specific triglyceride by less than 0.37. The first additive is preferably contained in an amount of 3.5 parts by mass or less per 100 parts by mass of the resin, inorganic filler, and specific triglyceride combined, since this allows the additive to be incorporated without inhibiting the water repellency exhibited by the specific triglyceride. From the perspective of improving leakproofness without impairing water repellency, the first additive is preferably contained in an amount of 0.01 to 3.5 parts by mass, more preferably 0.03 to 3.3 parts by mass, and even more preferably 0.06 to 3.2 parts by mass, per 100 parts by mass of the resin, inorganic filler, and specific triglyceride combined. The additive may also contain at least a second additive whose SP value differs from that of the specific triglyceride by 0.37 or more. The second additive is preferably contained in an amount of 10 parts by mass or less per 100 parts by mass of the resin, inorganic filler, and specific triglyceride combined, since this allows the additive to be incorporated without inhibiting the water repellency exhibited by the specific triglyceride. When the second additive is contained as an additive, the second additive is preferably contained in an amount of 0.01 to 10 parts by mass, more preferably 1 to 8 parts by mass, and even more preferably 1.5 to 6 parts by mass, per 100 parts by mass of the resin, inorganic filler, and specific triglyceride combined, from the viewpoint of improving leakproofness without impairing water repellency. As mentioned above, in the technical field of moisture-permeable films, such as the moisture-permeable film used in the present invention, triglycerides have been incorporated into moisture-permeable films. However, the inventors' investigations have revealed that randomly incorporating additives into a moisture-permeable film containing triglycerides inhibits the water repellency inherent to the triglycerides. In contrast, using the first additive in an amount of 3.5 parts by mass or less per 100 parts by mass of the resin, inorganic filler, and specific triglyceride, or using the second additive in an amount of 10 parts by mass or less per 100 parts by mass of the resin, inorganic filler, and specific triglyceride, allows the incorporation of the additive without inhibiting the water repellency exhibited by the specific triglyceride. To further enhance this advantage, the difference in SP value between the specific triglyceride and the second additive is preferably 0.50 or more, and even more preferably 0.60 or more. Furthermore, this difference is preferably 4.00 or less, even more preferably 3.00 or less, and even more preferably 1.50 or less.

[0097] The SP value is a physical property called the solubility parameter, and two substances with similar SP values ​​tend to mix well. In other words, two substances with similar SP values ​​are highly compatible. Therefore, when comparing the SP value of a specific triglyceride with the SP value of an additive, the SP value of the specific triglyceride may be larger, or the SP value of the additive may be larger. From the viewpoint of preventing the additive from impairing the water repellency of the specific triglyceride, it is preferable that the SP value of the specific triglyceride is larger than the SP value of the additive.

[0098] Examples of the first additive selected so that the difference in SP value from the specific triglyceride is less than 0.37 include some of the fatty acids, alcohols, monoesters, polyesters, and metal soaps exemplified above as dispersants, plasticizers, and pore-opening promoters.

[0099] Examples of the second additive selected so that the difference in SP value from the specific triglyceride is 0.37 or more include olefin oligomers, ethylene-α-olefin co-oligomers, low-molecular-weight polyethylene, silicone rubber, fluororubber, fluororesin, and polystyrene. In the present invention, the second additive alone may be used as the additive, or the second additive and the first additive may be used in combination. In some cases, the first additive alone may be used.

[0100] The SP value was calculated by the Fedors method [RFFEDORS, POLYM.ENG.SCI.14,147(1974)] and its unit is (cal / cm 3 ) 1 / 2 It is expressed as:

[0101] When the moisture-permeable film contains multiple types of specific triglycerides, the SP value δmix of the mixture shown below is calculated. δmix=Σδiφi(cal / cm 3 ) 1 / 2 In the above formula, δi represents the SP value of each component constituting the mixture, and φi represents the volume fraction of that component.

[0102] The moisture-permeable film is preferably one that is evaluated as having leakproof properties in the following leakproof property evaluation test. This allows the composite sheet of the present invention to have high leakproof properties. The moisture-permeable film described above can be one that is evaluated as having leakproof properties in the following leakproof property evaluation test. In the leakproofness evaluation test described below, the moisture-permeable film is fixed in a natural state to evaluate its leakproofness, but it is more preferable that the moisture-permeable film used in the present invention be evaluated as having leakproofness even when its leakproofness is evaluated in the same manner as the leakproofness evaluation test described below, except that it is fixed in an elongated state, such as a 30% elongation state, as in the examples described below. Stretchable moisture-permeable films tend to be more permeable to liquids in a stretched state than in a natural state, resulting in decreased leakproofness, but by exhibiting a certain level of leakproofness even in a stretched state in which leakproofness tends to be decreased, the composite sheet of the present invention can be imparted with high leakproofness.

[0103] (Leak prevention evaluation test) The evaluation object, a pulp sheet (Lead Healthy Cooking Paper Double (product name) manufactured by Lion Corporation, basis weight 40 g / m) was placed on a filter paper (No. 2 manufactured by Advantec Toyo Co., Ltd., diameter 70 mm). 2 ) are stacked in this order. The evaluation object is fixed in its natural state, and its size in plan view is adjusted so that its entire surface overlaps the filter paper. The pulp sheet is a rectangular shape in plan view, measuring 25 mm x 30 mm. 0.265 g of a wetting tension test mixture (manufactured by Kanto Chemical Co., Inc.) with a surface tension of 44 mN / m at 25°C is injected into the center of the upper surface of the pulp sheet using a dropper. Immediately after injection, a cylindrical acrylic resin plate with a diameter of 60 mm and a thickness of 5 mm is placed on the pulp sheet, and a 500 g weight is placed on the plate and pressure is applied for one hour. After one hour has passed since the weight was placed, the weight is removed, and the filter paper is visually observed for the presence or absence of the test liquid seeping out. The above series of operations is performed three times for the evaluation object. If no seeping out of the test liquid is observed on the filter paper in any of the three times, the evaluation object is evaluated as having leakproof properties; otherwise, it is evaluated as not having leakproof properties.

[0104] To add a little more about the leakproofness evaluation test, the evaluation object (moisture-permeable film) can be rectangular in plan view, larger than the size of the pulp sheet (25 mm x 30 mm). If this size cannot be prepared due to reasons such as the object being too small, a test piece is cut out of the largest similar shape to the square in plan view, and the test is performed by adjusting the pulp sheet and test liquid so that the surface pressure received by the pulp sheet and the amount of test liquid per unit area are equal. Furthermore, if the evaluation object is part of a product such as an absorbent article, the evaluation object is removed from the product with great care to avoid tears, etc., and then subjected to the test. If the test liquid injected onto the top surface of the pulp sheet overflows from the pulp sheet during pressure application and flows around the edge of the object to be evaluated and into the filter paper, a polyethylene film that is impermeable to the test liquid can be used to prevent the evaluation liquid from flowing around the edge of the object to be evaluated and into the filter paper.

[0105] The moisture-permeable film preferably has a flexibility deformation in the stretch direction (machine direction of the moisture-permeable film) measured by the tensile test of 0.060 N / (mm·(g / m 2 )) or less, more preferably 0.057N / (mm·(g / m 2 )) or less, more preferably 0.055 N / (mm (g / m 2 )) or less. This allows the composite sheet of the present invention to have high stretchability, and can be particularly stretchable. Furthermore, when the composite sheet of the present invention is used as a constituent member of an absorbent article, it can be stretched without interfering with the movement of the wearer of the absorbent article, thereby reducing the discomfort felt by the wearer. The moisture-permeable film described above can have a flexibility deformation degree in the stretch direction within the above range. On the other hand, the lower limit of the flexibility deformation degree in the stretch direction of the moisture-permeable film is preferably 0.005 N / (mm·(g / m) from the viewpoint of maintaining the strength of the composite sheet of the present invention. 2 ))That's all.

[0106] The moisture-permeable film preferably has a residual strain after 30% elongation measured by the tensile test of 11% or less, more preferably 10% or less, and even more preferably 9% or less. This allows the composite sheet of the present invention to have high stretchability and to be particularly prone to shrinkage. Furthermore, when the composite sheet of the present invention is used as a component of an absorbent article, the composite sheet follows the movements of the wearer of the absorbent article, thereby reducing discomfort to the wearer. The moisture-permeable film described above may have a residual strain after 30% elongation within the above range. Meanwhile, the lower limit of the residual strain after 30% elongation of the moisture-permeable film is the better, and 0% is most preferred.

[0107] The moisture-permeable film has moisture permeability and can transmit moisture. The moisture-permeable film preferably has a moisture permeability of 0.4 g / (100 cm) as measured in accordance with JIS L 1099 A-2. 2 ·h) or more, more preferably 0.45g / (100cm 2 ·h) or more, more preferably 0.8g / (100cm 2 ·h) or more. As a result, the composite sheet of the present invention has high moisture permeability, and when the composite sheet is used as a constituent member of an absorbent article, the moisture inside the absorbent article can be appropriately dissipated to the outside. The moisture permeability of the moisture-permeable film described above can be in the above range. On the other hand, the upper limit of the moisture permeability of the moisture-permeable film is preferably 4.5 g / (100 cm) from the viewpoint of preventing loss of leakproofness due to excessive porosity. 2 ·h) or less, more preferably 3.5g / (100cm 2 ·h) or less, more preferably 3.0 g / (100 cm 2 ·h) or less. The moisture permeability is measured by the following method.

[0108] (Method for measuring moisture permeability) This measurement method complies with JIS L 1099 A-2. 2Approximately 25 mL of ion-exchanged water is placed in a glass bottle (Labolan screw cap bottle No. 8, AS ONE), the mouth of the glass bottle is covered with one test piece so that there are no gaps, and the test piece (e.g., moisture-permeable film) is secured to the glass bottle with a rubber band to form the evaluation sample. After measuring the mass (W1) of the evaluation sample, the sample is stored in a thermostatic chamber controlled at 40°C and 20% RH for 10 to 15 hours. After storage, the mass (W2) of the evaluation sample is measured, the storage time (T1, unit: h) is recorded, and the moisture permeability is calculated using the following formula. Moisture permeability [g / (100cm 2 ·h)]={(W1-W2) / (T1×3.23)}×100

[0109] The air permeability of the moisture-permeable film in its natural state is preferably 3000 seconds or less, more preferably 2500 seconds or less. The air permeability is measured by the following method. The air permeability is measured using the time required for 25 cc of air to pass through the moisture-permeable film being evaluated in the thickness direction. The smaller the air permeability value, the higher the moisture permeability of the moisture-permeable film. A composite sheet including a moisture-permeable film having an air permeability within the above range can have high breathability. The moisture-permeable film described above can have an air permeability within the above range. On the other hand, the lower limit of the moisture-permeable film's air permeability in its natural state is preferably 1 second or more, from the viewpoint of maintaining the strength of the moisture-permeable film. Furthermore, since the moisture-permeable film used in the present invention has micropores and is stretchable, stretching the moisture-permeable film in its machine direction (stretching direction) can widen the micropores of the moisture-permeable film, thereby improving its breathability (reducing the air permeability value). Therefore, a preferred embodiment of the moisture-permeable film used in the present invention is a moisture-permeable film stretched in the machine direction (stretching direction). The stretching can be carried out according to a conventional method. The stretching ratio is not particularly limited, but can be, for example, 1.3 times.

[0110] (Method for measuring air permeability) This measurement method complies with JIS P8117. Using an air permeability tester (product name: Gurley Densometer, manufactured by Kumagai Riki Kogyo Co., Ltd.), the time required for 25 cc of air to permeate through the evaluation object (moisture-permeable film) in the thickness direction is measured. The evaluation object is in a natural state or in an elongated state (e.g., 30% elongated state) during the test. If the 25 cc of air has not completely permeated the moisture-permeable film even after 10,000 seconds or more have passed and the measurement is not completed, the measurement is deemed impossible, and the moisture-permeable film is evaluated as having no breathability.

[0111] Next, a preferred method for producing the moisture-permeable film used in the present invention will be described. A suitable method for producing a moisture-permeable film includes a step of stretching, at least uniaxially, a resin sheet obtained by melt-molding a compound containing a resin, an inorganic filler, and an additive. The details of the resin, inorganic filler, and additives contained in the compound are as described above. The blending amounts of the resin, inorganic filler, and additives contained in the compound are the same as the blending amounts of these components contained in the moisture-permeable film. Furthermore, the types and amounts of optional components contained in the compound are the same as the types and amounts of optional components contained in the moisture-permeable film.

[0112] The moisture-permeable film used in the present invention can be efficiently produced, for example, by the following method. First, the components constituting the compound described above are premixed using a Henschel mixer, super mixer, or the like, and then kneaded and pelletized using a single-screw or twin-screw extruder. The resulting pellets are then formed into a film using a molding machine to obtain a resin sheet. Examples of molding machines that can be used include T-die and inflation types.

[0113] The dispersant may be used alone or mixed with other components constituting the compound, but it is preferable to previously attach the dispersant to the surface of the inorganic filler to produce a surface-modified inorganic filler, and then mix this surface-modified inorganic filler with the other components constituting the compound to prepare the compound. In this way, the resin sheet can be successfully stretched while suppressing the occurrence of unintended pinholes, and a moisture-permeable film having both high moisture permeability and high water resistance can be obtained.

[0114] The resin sheet described above can be stretched uniaxially or biaxially to cause interfacial delamination between the resin and the inorganic filler, forming micropores. For this stretching, a roll method capable of stretching in the machine direction or a tenter method capable of stretching in both the machine direction and the film width direction can be used. In this manner, the moisture-permeable film used in the present invention can be obtained. To increase the area of ​​the resin sheet as it is stretched, the resin sheet is preferably stretched at least uniaxially by 1.1 times or more, more preferably by 1.5 times or more, and even more preferably by 2 times or more. Furthermore, to avoid a decrease in tear strength due to excessive molecular orientation caused by excessive stretching, the resin sheet is preferably stretched at 5.0 times or less, more preferably by 4.5 times or less, and even more preferably by 4 times or less.

[0115] In both the case of uniaxial stretching and biaxial stretching, the temperature of the resin film during stretching is preferably set to 30°C or higher and 100°C or lower, more preferably 35°C or higher and 95°C or lower, and even more preferably 40°C or higher and 90°C or lower, from the viewpoint of being able to stretch the film uniformly without breaking the film.

[0116] The present invention has been described above based on its preferred embodiments, but the present invention is not limited to the above embodiments and can be modified as appropriate within the scope of the invention. The following supplementary notes are further disclosed regarding the above-described embodiment of the present invention.

[0117] <1> a stretchable moisture-permeable film having micropores and a non-stretchable nonwoven fabric are overlapped and joined to each other at a plurality of joining portions scattered between the overlapping surfaces; The moisture-permeable film is stretchable, and the portion of the nonwoven fabric not joined to the moisture-permeable film stretches and contracts in accordance with the stretching and contraction of the moisture-permeable film. <2> In the natural state of the moisture-permeable film, the moisture-permeable film has a protruding portion protruding on the side opposite to the moisture-permeable film side, and a part or the whole of the protruding portion is the non-bonded portion of the nonwoven fabric. <1> The composite sheet according to claim 1. <3> In the natural state of the moisture-permeable film, the plurality of pleated convex portions extend in a direction intersecting the stretching direction of the moisture-permeable film, and between adjacent convex portions, concave portions having the joint portions at their bottoms extend in the same direction as the convex portions. <2> The composite sheet according to claim 1. <4> The convex portion is formed by the non-bonded portion of the nonwoven fabric protruding in a direction away from the moisture-permeable film, and has a hollow portion formed by a gap between the non-bonded portion and the moisture-permeable film. <2> or <3> The composite sheet according to claim 1. <5> The convex portions have a solid structure in which the constituent fibers of the nonwoven fabric are filled inside the convex portions. <2> or <3> The composite sheet according to claim 1. <6> The nonwoven fabric contains an olefin-based resin. <1> ~ <5> 10. The composite sheet according to claim 1 . <7> At the joint, the moisture-permeable film and the nonwoven fabric are joined with an adhesive. <1> ~ <6> 10. The composite sheet according to claim 1 . <8> The adhesive includes synthetic rubber. <7> The composite sheet according to claim 1. <9> The moisture-permeable film has, in addition to the micropores, pores having an opening diameter larger than that of the micropores. <1> ~ <8> 10. The composite sheet according to claim 1 . <10> The pore diameter is preferably 0.5 mm or more, more preferably 0.6 mm or more, and preferably 10 mm or less, more preferably 8 mm or less. <9> The composite sheet according to claim 1. <11> The pore size of the micropores is preferably 0.001 μm or more, more preferably 0.005 μm or more, and is preferably 500 μm or less, more preferably 300 μm or less. <1> ~ <10> 10. The composite sheet according to claim 1 .

[0118] <12> The moisture-permeable film is evaluated as having leak-proofness in a natural state in the leak-proofness evaluation test. <1> ~ <11> 10. The composite sheet according to claim 1 . <13> The flexibility deformation of the moisture-permeable film in the stretching direction (machine direction) is preferably 0.060 N / mm or less, more preferably 0.057 N / (mm·(g / m 2 )) or less, more preferably 0.055 N / mm or less, and preferably 0.005 N / mm or more. <1> ~ <12> 10. The composite sheet according to claim 1 . <14> The moisture-permeable film has a residual strain after 30% elongation of preferably 11% or less, more preferably 10% or less, even more preferably 9% or less, and preferably 0%. <1> ~ <13> 10. The composite sheet according to claim 1 . <15> The breathability of the moisture-permeable film in a natural state measured by the above method is preferably 3000 seconds or less, more preferably 2500 seconds or less, and preferably 1 second or more, in terms of the time required for 25 cc of air to permeate the moisture-permeable film in the thickness direction. <1> ~ <14> 10. The composite sheet according to claim 1 . <16> The moisture-permeable film preferably has a basis weight of 5 g / m 2 More preferably, 6 g / m 2 or more, and preferably 100 g / m 2 Less than 90 g / m 2The above-mentioned <1> ~ <15> 10. The composite sheet according to claim 1 . <17> The basis weight of the nonwoven fabric is preferably 5 g / m 2 More preferably, 6 g / m 2 or more, and preferably 100 g / m 2 Less than 90 g / m 2 The above-mentioned <1> ~ <16> 10. The composite sheet according to claim 1 .

[0119] <18> The moisture-permeable film contains a resin and an inorganic filler, The content of the inorganic filler in the moisture-permeable film is 50 parts by mass or more and 400 parts by mass or less with respect to 100 parts by mass of the resin in the moisture-permeable film. <1> ~ <17> 10. The composite sheet according to claim 1 . <19> The resin has a density of 0.840 g / cm 3 More than 0.900g / cm 3 The olefin-based resin composition contains less than <18> The composite sheet according to claim 1. <20> The density of the olefin resin composition is preferably 0.850 g / cm 3 More than 0.895g / cm 3 or less, more preferably 0.860 g / cm 3 More than 0.885g / cm 3 The above-mentioned <19> The composite sheet according to claim 1. <21> The olefin resin composition contains a low-melting-point olefin resin having a melting point of less than 90°C and a high-melting-point olefin resin having a melting point of 95°C or higher. <19> or <20> The composite sheet according to claim 1. <22> The moisture-permeable film contains a pore-opening promoter in an amount of 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of a resin in the moisture-permeable film, and the pore-opening promoter is a metal soap. <18> ~ <21> 10. The composite sheet according to claim 1 .

[0120] <23> The moisture-permeable film contains 0.1 parts by mass or more and 30 parts by mass or less of a triglyceride relative to 100 parts by mass of a resin in the moisture-permeable film, the triglyceride containing a group derived from a fatty acid having 16 to 22 carbon atoms, the group being a hydrocarbon group having no unsaturated bond and no substituent. <18> ~ <22> 10. The composite sheet according to claim 1 . <24> The triglyceride is a mixture of a triglyceride containing at least a group derived from a fatty acid having 18 carbon atoms in one molecule and a triglyceride containing at least a group derived from a fatty acid having 16 to 22 carbon atoms in one molecule (excluding fatty acids having 18 carbon atoms). <23> The composite sheet according to claim 1. <25> The triglyceride contains, in one molecule, at least one group derived from a saturated fatty acid having 18 carbon atoms and at least one group derived from a saturated fatty acid having 16 to 22 carbon atoms (excluding fatty acids having 18 carbon atoms). <23> The composite sheet according to claim 1. <26> Preferably, 28% by mass or more and 96% by mass or less, more preferably 28% by mass or more and 70% by mass or less, and even more preferably 29% by mass or more and 67% by mass or less of the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film are groups derived from fatty acids having 18 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds and no substituents). <23> ~ <25> 10. The composite sheet according to claim 1 . <27> With respect to the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film, 28% by mass or more and 68% by mass or less are groups derived from fatty acids having 18 carbon atoms, and 26% by mass or more and 70% by mass or less are groups derived from fatty acids having 16 carbon atoms. <23> ~ <26> 10. The composite sheet according to claim 1 . <28> With respect to the total amount of groups derived from fatty acids contained in all triglycerides in the moisture-permeable film, 28% by mass or more and 47% by mass or less are groups derived from fatty acids having 18 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds and no substituents), and 40% by mass or more and 60% by mass or less are groups derived from fatty acids having 22 carbon atoms (these groups are hydrocarbon groups having no unsaturated bonds and no substituents). <23> ~ <26> 10. The composite sheet according to claim 1 . <29> The moisture-permeable film is a film in which all triglycerides in the film are derived from fatty acids and each triglyceride is a hydrocarbon group having no unsaturated bond. <23> ~ <28> 10. The composite sheet according to claim 1 . <30> the groups derived from fatty acids contained in all triglycerides in the moisture-permeable film are hydrocarbon groups having no substituents; <23> ~ <29> 10. The composite sheet according to claim 1 . <31> The aforementioned <1> ~ <30> An absorbent article comprising the composite sheet according to any one of the preceding claims. <32> The absorbent article has a vertical direction extending from the wearer's abdomen side through the crotch region to the back side, and a horizontal direction perpendicular to the vertical direction, The composite sheet has stretchability in the longitudinal direction or the transverse direction. <31> The absorbent article according to claim 1. [Example]

[0121] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to these examples.

[0122] [Production of moisture-permeable films A to E] The components listed in the "Raw Materials" column of Table 1 below were weighed out in the amounts shown in the table. These were mixed in a Henschel mixer (manufactured by Kawata Co., Ltd.). The resulting mixture was kneaded in a twin-screw extruder (manufactured by Toyo Seiki Seisakusho) at a set temperature of 180°C and a screw rotation speed of 180 rpm to obtain a pelletized compound. The resulting compound was used to produce a moisture-permeable film. Specifically, the compound was first used as a raw material, and a resin sheet was molded from the molten compound at a blow ratio of 2.5 using an inflation molding machine with a 100 mm diameter slit at the die outlet and a 0.9 mm gap. The die temperature was set to 200°C, and the take-up speed was 10 m / min. The molded resin sheet was then uniaxially stretched in the machine direction using a roll stretching machine to obtain moisture-permeable films A to E with the basis weights shown in Table 1. The stretching ratios and stretching temperatures are as shown in the table. Moisture-permeable films A to D all have micropores and are stretchable in the stretching direction (machine direction). On the other hand, moisture-permeable film E has micropores but is not stretchable.

[0123] Details of the raw materials used in the production of moisture-permeable films A to E are as follows. Olefin resin A (corresponding to the low-melting-point olefin resin): ethylene-α-olefin copolymer produced with a metallocene catalyst, melting point 44°C, resin density 0.864 g / cm 3 Olefin resin B (corresponding to the high-melting-point olefin resin mentioned above): Linear low-density polyethylene produced with a metallocene catalyst, melting point 116°C, resin density 0.924 g / cm 3 Inorganic filler: calcium carbonate, average particle size D50: 1.8 μm Dispersant: stearic acid Specific triglycerides: Palm oil (C14: 1%, C16: 42%, C18: 57%) Pore ​​opening promoter (metal soap): zinc stearate, precipitation temperature 102°C, melting point 124°C

[0124] The physical properties of moisture-permeable films A to E were measured. The physical properties of moisture-permeable film F (urethane elastomer film, manufactured by Okura Kogyo Co., Ltd., Silklon ES85), which does not have micropores and has elasticity, were also measured. The results are shown in Table 1. The air permeability was measured using the above-mentioned method for measuring air permeability. The state of the evaluation object (moisture-permeable film) during measurement was in two types: a natural state and a state stretched 1.3 times in one direction (machine direction) in which it can stretch (30% stretched state). Note that the breathability of moisture-permeable film F was too low, so the breathability could not be measured. In addition, moisture-permeable film E was not stretchable, so the breathability in the stretched state was not evaluated. Leakproofness was evaluated using the leakproofness evaluation test described above. However, the moisture-permeable films to be evaluated were in their natural state or in a state stretched by 30%. Furthermore, in addition to a test liquid having a surface tension of 44 mN / m at 25°C, a test liquid having a surface tension of 35 mN / m at 25°C was used as a more severe test liquid. These test liquids were mixed liquids for wetting tension testing manufactured by Kanto Chemical Co., Inc. In the "Leakproofness" column of Table 1, "A" indicates leakproofness and "B" indicates no leakproofness. Since moisture-permeable film E does not have stretchability, leakproofness in a stretched state was not evaluated.

[0125] [Table 1]

[0126] [Examples 1 and 2, Comparative Example 1: Production of Composite Sheet] Using moisture-permeable film C or F and a non-stretchable nonwoven fabric, a composite sheet was produced by the above-mentioned production method A or B, i.e., "a composite sheet in which, in the natural state of the film, the non-bonded portions of the nonwoven fabric with respect to the film form a plurality of partial or entire pleated convex portions that protrude toward the side opposite the film and extend in one direction, and between adjacent convex portions, concave portions having at their bottom the bonded portions between the film and nonwoven fabric extend in the same direction as the convex portions." In the manufacturing method of the composite sheet by manufacturing method A, the moisture-permeable film is stretched by 60% in the machine direction, and 10 g / m of adhesive is applied in a summit shape to one side of the stretched moisture-permeable film. 2 The moisture-permeable film was then released from its stretched state to produce the desired composite sheet. In the manufacturing method of the composite sheet by manufacturing method B, the moisture-permeable film is in an unstretched state, and 4 g / m of adhesive is applied in a summit shape to one side in advance. 2 The composite sheet precursor was then subjected to groove stretching using a pair of grooved rolls at a push-in depth of 3.7 mm and a conveying speed after the grooves of 10 m / min to produce the desired composite sheet. In the manufacturing method A, the non-stretchable nonwoven fabric is made of olefin-based resin fibers having a basis weight of 17 g / m 2 In the manufacturing method B, the non-stretchable nonwoven fabric was a spunbond nonwoven fabric having a basis weight of 29 g / m2, the constituent fibers of which were made of an olefin resin. 2 The air-through nonwoven fabric was used. The adhesive used was a hot melt adhesive containing synthetic rubber.

[0127] [Performance evaluation of composite sheets] The composite sheets of each Example and Comparative Example were evaluated for breathability, moisture permeability, leakproofness, and stretchability by the following methods. The results are shown in Table 2 below.

[0128] (Method for evaluating breathability of composite sheets) The air permeability of the composite sheet (the time required for 25 cc of air to pass through the composite sheet in the thickness direction) was measured according to the above-mentioned method for measuring air permeability. However, the composite sheet was stretched 1.3 times in one direction in which it could stretch (30% stretched state) during the measurement. Air permeability of 3000 seconds or less was rated A (highest rating for breathability), and all other cases were rated B.

[0129] (Method for evaluating the moisture permeability of composite sheets) The moisture permeability of the composite sheet was measured in accordance with the moisture permeability measurement method described above. That is, the measurement was carried out using the composite sheet as a test piece in the moisture permeability measurement method described above. 2 ·h) or more was rated A (highest rating for breathability), and all other cases were rated B.

[0130] (Method for evaluating the leak-proofness of composite sheets) The leakproofness of the composite sheet was evaluated in accordance with the leakproofness evaluation test described above. That is, in the leakproofness evaluation test described above, a composite sheet was used as the evaluation object, and the test was performed while the composite sheet was stretched 1.3 times (30% stretched state) in one direction (machine direction) in which it was stretchable. The test was performed three times for each type of evaluation object, and if no seepage of the test liquid was observed on the filter paper in any of the three tests, it was given an A (highest rating for leakproofness), and if not, it was given a B.

[0131] (Method for evaluating the elasticity of composite sheets) The residual strain after 30% elongation of the composite sheet was measured in accordance with the cycle test in the tensile test. That is, the cycle test was performed using the composite sheet as the evaluation object. For one type of evaluation object, the residual strain after 30% elongation was measured in two directions, the "machine direction" (the flow direction during the manufacture of the evaluation object) and the "direction perpendicular to the machine direction." If either of the residual strains after 30% elongation in the two directions was 11% or less, it was rated A (the highest rating for stretchability), and otherwise it was rated B.

[0132] [Table 2]

[0133] As shown in Table 2, the composite sheets of each Example had moisture-permeable film C having micropores as the constituent film, and therefore had superior breathability compared to Comparative Example 1, in which the moisture-permeable film was moisture-permeable film F, which was non-porous and exhibited no breathability at all. Furthermore, the composite sheets of each Example and Comparative Example all had regularly arranged convex portions and concave portions (non-joined portions of the nonwoven fabric) on the surface facing the nonwoven fabric, similar to the composite sheet 1 shown in Figure 1, and therefore had a good feel and appearance on that surface. [Explanation of symbols]

[0134] 1,1A,1B composite sheet 2. Breathable film 3. Nonwoven fabric 31 Non-bonded parts of nonwoven fabric 4 Joint 5 Convex part 6 recess 7 Hollow part 10 Disposable diapers (absorbent articles) 11 Absorbent body 20 Exterior body 21 Outer layer sheet 21A Ventral outer sheet 21B crotch outer layer sheet 21C Dorsal outer layer sheet 22 Inner layer sheet

Claims

1. a stretchable moisture-permeable film having micropores and a non-stretchable nonwoven fabric are overlapped and joined to each other at a plurality of joining portions scattered between the overlapping surfaces; The moisture-permeable film is stretchable, and the portion of the nonwoven fabric not joined to the moisture-permeable film stretches in accordance with the stretching of the moisture-permeable film.

2. 2. The composite sheet according to claim 1, wherein in the natural state of the moisture-permeable film, a convex portion protruding on a side opposite to the moisture-permeable film side is provided, and a part or the entirety of the convex portion is the non-jointed portion of the nonwoven fabric.

3. 3. The composite sheet according to claim 2, wherein, in the natural state of the moisture permeable film, the plurality of pleated convex portions extend in a direction intersecting a stretching direction of the moisture permeable film, and between adjacent convex portions, concave portions having the joint portion at their bottoms extend in the same direction as the convex portions.

4. The composite sheet according to claim 2 , wherein the convex portion is formed by the non-jointed portion of the nonwoven fabric protruding in a direction away from the moisture-permeable film, and has a hollow portion formed by a gap between the non-jointed portion and the moisture-permeable film.

5. The composite sheet according to claim 2 , wherein the protrusions have a solid structure in which constituent fibers of the nonwoven fabric are filled inside the protrusions.

6. The composite sheet according to claim 1 , wherein the nonwoven fabric comprises an olefin-based resin.

7. The composite sheet according to claim 1 , wherein the moisture-permeable film and the nonwoven fabric are joined at the joint with an adhesive.

8. The composite sheet of claim 7 , wherein the adhesive comprises a synthetic rubber.

9. The composite sheet according to claim 1 , wherein the moisture-permeable film has pores, in addition to the micropores, the pores having an opening diameter larger than that of the micropores.

10. The moisture-permeable film contains a resin and an inorganic filler, The composite sheet according to claim 1 , wherein the content of the inorganic filler in the moisture-permeable film is 50 parts by mass or more and 400 parts by mass or less per 100 parts by mass of the resin in the moisture-permeable film.

11. The resin has a density of 0.840 g / cm 3 0.900g / cm or more 3 11. The composite sheet of claim 10 comprising an olefin-based resin composition of less than 1000 parts by weight.

12. The composite sheet according to claim 11, wherein the olefin-based resin composition contains a low-melting-point olefin-based resin having a melting point of less than 90°C and a high-melting-point olefin-based resin having a melting point of 95°C or higher.

13. The composite sheet according to claim 10 , wherein the moisture permeable film contains a pore opening promoter in an amount of 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the resin in the moisture permeable film, and the pore opening promoter is a metal soap.

14. 11. The composite sheet according to claim 10, wherein the moisture permeable film contains a triglyceride in an amount of 0.1 parts by mass or more and 30 parts by mass or less per 100 parts by mass of the resin in the moisture permeable film, the triglyceride containing a group derived from a fatty acid having 16 to 22 carbon atoms, the group being a hydrocarbon group having no unsaturated bond and no substituent.

15. An absorbent article comprising the composite sheet according to any one of claims 1 to 14.

16. The absorbent article has a vertical direction extending from a wearer's abdomen side through a crotch region to a back side, and a horizontal direction perpendicular to the vertical direction, The absorbent article according to claim 15 , wherein the composite sheet has elasticity in the longitudinal direction or the transverse direction.